Magnetotropic susceptibility - Shekhter, A.; Mcdonald, R. D.; Ramshaw, B. J.; Modic, Kimberly A (Physical Review B)
The magnetotropic susceptibility is the thermodynamic coefficient associated with the rotational anisotropy of the free energy in an external magnetic field and is closely related to the magnetic susceptibility. It emerges naturally in frequency-shift measurements of oscillating mechanical cantilevers, which are becoming an increasingly important tool in the quantitative study of the thermodynamics of modern condensed-matter systems. Here we discuss the basic properties of the magnetotropic susceptibility as they relate to the experimental aspects of frequency-shift measurements, as well as to the interpretation of those experiments in terms of the intrinsic properties of the system under study.

Special Collection: Photocatalytic synthesis - Næsborg, Line; Pieber, Bartholomäus; Wenger, Oliver S. (ChemCatChem)
This Special Collection is dedicated to the field of photocatalytic synthesis and contains a diverse selection of original research contributions. It includes studies on catalyst development, mechanistic investigations, method development and the use of enabling technologies, illustrating the many facets of state-of-the-art research in photocatalytic synthesis. Further, emerging topics are surveyed and discussed in three reviews and a concept article.

Optical and electronic signal stabilization of plasmonic fiber optic gate electrodes: Towards improved real-time dual-mode biosensing - Hasler, Roger; Steger-Polt, Marie Helene; Reiner-Rozman, Ciril; Fossati, Stefan; Lee, Seungho; Aspermair, Patrik; Kleber, Christoph; Ibáñez, Maria; Dostalek, Jakub; Knoll, Wolfgang (Frontiers in Physics)
The use of multimodal readout mechanisms next to label-free real-time monitoring of biomolecular interactions can provide valuable insight into surface-based reaction mechanisms. To this end, the combination of an electrolyte-gated field-effect transistor (EG-FET) with a fiber optic-coupled surface plasmon resonance (FO-SPR) probe serving as gate electrode has been investigated to deconvolute surface mass and charge density variations associated to surface reactions. However, applying an electrochemical potential on such gold-coated FO-SPR gate electrodes can induce gradual morphological changes of the thin gold film, leading to an irreversible blue-shift of the SPR wavelength and a substantial signal drift. We show that mild annealing leads to optical and electronic signal stabilization (20-fold lower signal drift than as-sputtered fiber optic gates) and improved overall analytical performance characteristics. The thermal treatment prevents morphological changes of the thin gold-film occurring during operation, hence providing reliable and stable data immediately upon gate voltage application. Thus, the readout output of both transducing principles, the optical FO-SPR and electronic EG-FET, stays constant throughout the whole sensing time-window and the long-term effect of thermal treatment is also improved, providing stable signals even after 1 year of storage. Annealing should therefore be considered a necessary modification for applying fiber optic gate electrodes in real-time multimodal investigations of surface reactions at the solid-liquid interface.

On unsteady internal flows of incompressible fluids characterized by implicit constitutive equations in the bulk and on the boundary - Bulíček, Miroslav; Málek, Josef; Maringová, Erika (Journal of Mathematical Fluid Mechanics)
Long-time and large-data existence of weak solutions for initial- and boundary-value problems concerning three-dimensional flows of incompressible fluids is nowadays available not only for Navier–Stokes fluids but also for various fluid models where the relation between the Cauchy stress tensor and the symmetric part of the velocity gradient is nonlinear. The majority of such studies however concerns models where such a dependence is explicit (the stress is a function of the velocity gradient), which makes the class of studied models unduly restrictive. The same concerns boundary conditions, or more precisely the slipping mechanisms on the boundary, where the no-slip is still the most preferred condition considered in the literature. Our main objective is to develop a robust mathematical theory for unsteady internal flows of implicitly constituted incompressible fluids with implicit relations between the tangential projections of the velocity and the normal traction on the boundary. The theory covers numerous rheological models used in chemistry, biorheology, polymer and food industry as well as in geomechanics. It also includes, as special cases, nonlinear slip as well as stick–slip boundary conditions. Unlike earlier studies, the conditions characterizing admissible classes of constitutive equations are expressed by means of tools of elementary calculus. In addition, a fully constructive proof (approximation scheme) is incorporated. Finally, we focus on the question of uniqueness of such weak solutions.

3D cell segregation geometry and dynamics are governed by tissue surface tension regulation - Méhes, Elod; Mones, Enys; Varga, Máté; Zsigmond, Áron; Biri-Kovács, Beáta; Nyitray, László; Barone, Vanessa; Krens, Gabriel; Heisenberg, Carl-Philipp J; Vicsek, Tamás (Communications Biology)
Tissue morphogenesis and patterning during development involve the segregation of cell types. Segregation is driven by differential tissue surface tensions generated by cell types through controlling cell-cell contact formation by regulating adhesion and actomyosin contractility-based cellular cortical tensions. We use vertebrate tissue cell types and zebrafish germ layer progenitors as in vitro models of 3-dimensional heterotypic segregation and developed a quantitative analysis of their dynamics based on 3D time-lapse microscopy. We show that general inhibition of actomyosin contractility by the Rho kinase inhibitor Y27632 delays segregation. Cell type-specific inhibition of non-muscle myosin2 activity by overexpression of myosin assembly inhibitor S100A4 reduces tissue surface tension, manifested in decreased compaction during aggregation and inverted geometry observed during segregation. The same is observed when we express a constitutively active Rho kinase isoform to ubiquitously keep actomyosin contractility high at cell-cell and cell-medium interfaces and thus overriding the interface-specific regulation of cortical tensions. Tissue surface tension regulation can become an effective tool in tissue engineering.

The membrane surface as a platform that organizes cellular and biochemical processes - Leonard, Thomas A.; Loose, Martin; Martens, Sascha (Developmental Cell)
Membranes are essential for life. They act as semi-permeable boundaries that define cells and organelles. In addition, their surfaces actively participate in biochemical reaction networks, where they confine proteins, align reaction partners, and directly control enzymatic activities. Membrane-localized reactions shape cellular membranes, define the identity of organelles, compartmentalize biochemical processes, and can even be the source of signaling gradients that originate at the plasma membrane and reach into the cytoplasm and nucleus. The membrane surface is, therefore, an essential platform upon which myriad cellular processes are scaffolded. In this review, we summarize our current understanding of the biophysics and biochemistry of membrane-localized reactions with particular focus on insights derived from reconstituted and cellular systems. We discuss how the interplay of cellular factors results in their self-organization, condensation, assembly, and activity, and the emergent properties derived from them.

The Ycf48 accessory factor occupies the site of the oxygen-evolving manganese cluster during photosystem II biogenesis - Zhao, Ziyu; Vercellino, Irene; Knoppová, Jana; Sobotka, Roman; Murray, James W.; Nixon, Peter J.; Sazanov, Leonid A; Komenda, Josef (Nature Communications)
Robust oxygenic photosynthesis requires a suite of accessory factors to ensure efficient assembly and repair of the oxygen-evolving photosystem two (PSII) complex. The highly conserved Ycf48 assembly factor binds to the newly synthesized D1 reaction center polypeptide and promotes the initial steps of PSII assembly, but its binding site is unclear. Here we use cryo-electron microscopy to determine the structure of a cyanobacterial PSII D1/D2 reaction center assembly complex with Ycf48 attached. Ycf48, a 7-bladed beta propeller, binds to the amino-acid residues of D1 that ultimately ligate the water-oxidising Mn4CaO5 cluster, thereby preventing the premature binding of Mn2+ and Ca2+ ions and protecting the site from damage. Interactions with D2 help explain how Ycf48 promotes assembly of the D1/D2 complex. Overall, our work provides valuable insights into the early stages of PSII assembly and the structural changes that create the binding site for the Mn4CaO5 cluster.

Stopping criteria for value iteration on stochastic games with quantitative objectives - Kretinsky, Jan; Meggendorfer, Tobias; Weininger, Maximilian (38th Annual ACM/IEEE Symposium on Logic in Computer Science)
A classic solution technique for Markov decision processes (MDP) and stochastic games (SG) is value iteration (VI). Due to its good practical performance, this approximative approach is typically preferred over exact techniques, even though no practical bounds on the imprecision of the result could be given until recently. As a consequence, even the most used model checkers could return arbitrarily wrong results. Over the past decade, different works derived stopping criteria, indicating when the precision reaches the desired level, for various settings, in particular MDP with reachability, total reward, and mean payoff, and SG with reachability.In this paper, we provide the first stopping criteria for VI on SG with total reward and mean payoff, yielding the first anytime algorithms in these settings. To this end, we provide the solution in two flavours: First through a reduction to the MDP case and second directly on SG. The former is simpler and automatically utilizes any advances on MDP. The latter allows for more local computations, heading towards better practical efficiency.Our solution unifies the previously mentioned approaches for MDP and SG and their underlying ideas. To achieve this, we isolate objective-specific subroutines as well as identify objective-independent concepts. These structural concepts, while surprisingly simple, form the very essence of the unified solution.

Concepts, mechanisms and implications of long-term epigenetic inheritance - Hollwey, Elizabeth; Briffa, Amy; Howard, Martin; Zilberman, Daniel (Current Opinion in Genetics and Development)
Many modes and mechanisms of epigenetic inheritance have been elucidated in eukaryotes. Most of them are relatively short-term, generally not exceeding one or a few organismal generations. However, emerging evidence indicates that one mechanism, cytosine DNA methylation, can mediate epigenetic inheritance over much longer timescales, which are mostly or completely inaccessible in the laboratory. Here we discuss the evidence for, and mechanisms and implications of, such long-term epigenetic inheritance. We argue that compelling evidence supports the long-term epigenetic inheritance of gene body methylation, at least in the model angiosperm Arabidopsis thaliana, and that variation in such methylation can therefore serve as an epigenetic basis for phenotypic variation in natural populations.

The molecular basis of sexual dimorphism: Experimental and theoretical characterization of phenotypic, transcriptomic and genetic patterns of sex-specific adaptation - Puixeu Sala, Gemma
Females and males across species are subject to divergent selective pressures arising from di↵erent reproductive interests and ecological niches. This often translates into a intricate array of sex-specific natural and sexual selection on traits that have a shared genetic basis between both sexes, causing a genetic sexual conflict. The resolution of this conflict mostly relies on the evolution of sex-specific expression of the shared genes, leading to phenotypic sexual dimorphism. Such sex-specific gene expression is thought to evolve via modifications of the genetic networks ultimately linked to sex-determining transcription factors. Although much empirical and theoretical evidence supports this standard picture of the molecular basis of sexual conflict resolution, there still are a few open questions regarding the complex array of selective forces driving phenotypic di↵erentiation between the sexes, as well as the molecular mechanisms underlying sexspecific adaptation. I address some of these open questions in my PhD thesis. First, how do patterns of phenotypic sexual dimorphism vary within populations, as a response to the temporal and spatial changes in sex-specific selective forces? To tackle this question, I analyze the patterns of sex-specific phenotypic variation along three life stages and across populations spanning the whole geographical range of Rumex hastatulus, a wind-pollinated angiosperm, in the first Chapter of the thesis. Second, how do gene expression patterns lead to phenotypic dimorphism, and what are the molecular mechanisms underlying the observed transcriptomic variation? I address this question by examining the sex- and tissue-specific expression variation in newly-generated datasets of sex-specific expression in heads and gonads of Drosophila melanogaster. I additionally used two complementary approaches for the study of the genetic basis of sex di↵erences in gene expression in the second and third Chapters of the thesis. Third, how does intersex correlation, thought to be one of the main aspects constraining the ability for the two sexes to decouple, interact with the evolution of sexual dimorphism? I develop models of sex-specific stabilizing selection, mutation and drift to formalize common intuition regarding the patterns of covariation between intersex correlation and sexual dimorphism in the fourth Chapter of the thesis. Alltogether, the work described in this PhD thesis provides useful insights into the links between genetic, transcriptomic and phenotypic layers of sex-specific variation, and contributes to our general understanding of the dynamics of sexual dimorphism evolution.

Sex-specific estimation of cis and trans regulation of gene expression in heads and gonads of Drosophila melanogaster - Puixeu Sala, Gemma; Macon, Ariana; Vicoso, Beatriz (G3: Genes, Genomes, Genetics)
The regulatory architecture of gene expression is known to differ substantially between sexes in Drosophila, but most studies performed so far used whole-body data and only single crosses, which may have limited their scope to detect patterns that are robust across tissues and biological replicates. Here, we use allele-specific gene expression of parental and reciprocal hybrid crosses between 6 Drosophila melanogaster inbred lines to quantify cis- and trans-regulatory variation in heads and gonads of both sexes separately across 3 replicate crosses. Our results suggest that female and male heads, as well as ovaries, have a similar regulatory architecture. On the other hand, testes display more and substantially different cis-regulatory effects, suggesting that sex differences in the regulatory architecture that have been previously observed may largely derive from testis-specific effects. We also examine the difference in cis-regulatory variation of genes across different levels of sex bias in gonads and heads. Consistent with the idea that intersex correlations constrain expression and can lead to sexual antagonism, we find more cis variation in unbiased and moderately biased genes in heads. In ovaries, reduced cis variation is observed for male-biased genes, suggesting that cis variants acting on these genes in males do not lead to changes in ovary expression. Finally, we examine the dominance patterns of gene expression and find that sex- and tissue-specific patterns of inheritance as well as trans-regulatory variation are highly variable across biological crosses, although these were performed in highly controlled experimental conditions. This highlights the importance of using various genetic backgrounds to infer generalizable patterns.
Keywords: Genetics (clinical); Genetics; Molecular Biology

ZnUMBA - a live imaging method to detect local barrier breaches - Higashi, Tomohito; Stephenson, Rachel E.; Schwayer, Cornelia; Huljev, Karla; Higashi, Atsuko Y.; Heisenberg, Carl-Philipp J; Chiba, Hideki; Miller, Ann L. (Journal of Cell Science)
Epithelial barrier function is commonly analyzed using transepithelial electrical resistance, which measures ion flux across a monolayer, or by adding traceable macromolecules and monitoring their passage across the monolayer. Although these methods measure changes in global barrier function, they lack the sensitivity needed to detect local or transient barrier breaches, and they do not reveal the location of barrier leaks. Therefore, we previously developed a method that we named the zinc-based ultrasensitive microscopic barrier assay (ZnUMBA), which overcomes these limitations, allowing for detection of local tight junction leaks with high spatiotemporal resolution. Here, we present expanded applications for ZnUMBA. ZnUMBA can be used in Xenopus embryos to measure the dynamics of barrier restoration and actin accumulation following laser injury. ZnUMBA can also be effectively utilized in developing zebrafish embryos as well as cultured monolayers of Madin–Darby canine kidney (MDCK) II epithelial cells. ZnUMBA is a powerful and flexible method that, with minimal optimization, can be applied to multiple systems to measure dynamic changes in barrier function with spatiotemporal precision.

Practical limitations of Ethereum’s layer-2 - Neiheiser, Ray; Inacio, Gustavo; Rech, Luciana; Montez, Carlos; Matos, Miguel; Rodrigues, Luis (IEEE Access)
Most permissionless blockchains inherently suffer from throughput limitations. Layer-2 systems, such as side-chains or Rollups, have been proposed as a possible strategy to overcome this limitation. Layer-2 systems interact with the main-chain in two ways. First, users can move funds from/to the main-chain to/from the layer-2. Second, layer-2 systems periodically synchronize with the main-chain to keep some form of log of their activity on the main-chain - this log is key for security. Due to this interaction with the main-chain, which is necessary and recurrent, layer-2 systems impose some load on the main-chain. The impact of such load on the main-chain has been, so far, poorly understood. In addition to that, layer-2 approaches typically sacrifice decentralization and security in favor of higher throughput. This paper presents an experimental study that analyzes the current state of Ethereum layer-2 projects. Our goal is to assess the load they impose on Ethereum and to understand their scalability potential in the long-run. Our analysis shows that the impact of any given layer-2 on the main-chain is the result of both technical aspects (how state is logged on the main-chain) and user behavior (how often users decide to transfer funds between the layer-2 and the main-chain). Based on our observations, we infer that without efficient mechanisms that allow users to transfer funds in a secure and fast manner directly from one layer-2 project to another, current layer-2 systems will not be able to scale Ethereum effectively, regardless of their technical solutions. Furthermore, from our results, we conclude that the layer-2 systems that offer similar security guarantees as Ethereum have limited scalability potential, while approaches that offer better performance, sacrifice security and lead to an increase in centralization which runs against the end-goals of permissionless blockchains.
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Data from: Sex-specific estimation of cis and trans regulation of gene expression in heads and gonads of Drosophila melanogaster - Puixeu Sala, Gemma
Datasets of the publication "Sex-specific estimation of cis and trans regulation of gene expression in heads and gonads of Drosophila melanogaster".

Horospherical coordinates of lattice points in hyperbolic spaces: Effective counting and equidistribution - Horesh, Tal; Nevo, Amos (Pacific Journal of Mathematics)
We establish effective counting results for lattice points in families of domains in real, complex and quaternionic hyperbolic spaces of any dimension. The domains we focus on are defined as product sets with respect to an Iwasawa decomposition. Several natural diophantine problems can be reduced to counting lattice points in such domains. These include equidistribution of the ratio of the length of the shortest solution (x,y) to the gcd equation bx−ay=1 relative to the length of (a,b), where (a,b) ranges over primitive vectors in a disc whose radius increases, the natural analog of this problem in imaginary quadratic number fields, as well as equidistribution of integral solutions to the diophantine equation defined by an integral Lorentz form in three or more variables. We establish an effective rate of convergence for these equidistribution problems, depending on the size of the spectral gap associated with a suitable lattice subgroup in the isometry group of the relevant hyperbolic space. The main result underlying our discussion amounts to establishing effective joint equidistribution for the horospherical component and the radial component in the Iwasawa decomposition of lattice elements.

Emergence of a Bose polaron in a small ring threaded by the Aharonov-Bohm flux - Brauneis, Fabian; Ghazaryan, Areg; Hammer, Hans-Werner; Volosniev, Artem (Communications Physics)
The model of a ring threaded by the Aharonov-Bohm flux underlies our understanding of a coupling between gauge potentials and matter. The typical formulation of the model is based upon a single particle picture, and should be extended when interactions with other particles become relevant. Here, we illustrate such an extension for a particle in an Aharonov-Bohm ring subject to interactions with a weakly interacting Bose gas. We show that the ground state of the system can be described using the Bose-polaron concept—a particle dressed by interactions with a bosonic environment. We connect the energy spectrum to the effective mass of the polaron, and demonstrate how to change currents in the system by tuning boson-particle interactions. Our results suggest the Aharonov-Bohm ring as a platform for studying coherence and few- to many-body crossover of quasi-particles that arise from an impurity immersed in a medium.
Keywords: General Physics and Astronomy

Homological Bondal-Orlov localization conjecture for rational singularities - Mauri, Mirko; Shinder, Evgeny (Forum of Mathematics, Sigma)
Given a resolution of rational singularities π:X~→X over a field of characteristic zero, we use a Hodge-theoretic argument to prove that the image of the functor Rπ∗:Db(X~)→Db(X) between bounded derived categories of coherent sheaves generates Db(X) as a triangulated category. This gives a weak version of the Bondal–Orlov localization conjecture [BO02], answering a question from [PS21]. The same result is established more generally for proper (not necessarily birational) morphisms π:X~→X , with X~ smooth, satisfying Rπ∗(OX~)=OX .

On the global minimum of the energy–momentum relation for the polaron - Lampart, Jonas; Mitrouskas, David Johannes; Mysliwy, Krzysztof (Mathematical Physics, Analysis and Geometry)
For the Fröhlich model of the large polaron, we prove that the ground state energy as a function of the total momentum has a unique global minimum at momentum zero. This implies the non-existence of a ground state of the translation invariant Fröhlich Hamiltonian and thus excludes the possibility of a localization transition at finite coupling.
Keywords: Geometry and Topology; Mathematical Physics

Nonadiabatic laser-induced alignment dynamics of molecules on a surface - Kranabetter, Lorenz; Kristensen, Henrik H.; Ghazaryan, Areg; Schouder, Constant A.; Chatterley, Adam S.; Janssen, Paul; Jensen, Frank; Zillich, Robert E.; Lemeshko, Mikhail; Stapelfeldt, Henrik (Physical Review Letters)
We demonstrate that a sodium dimer, Na2(13Σ+u), residing on the surface of a helium nanodroplet, can be set into rotation by a nonresonant 1.0 ps infrared laser pulse. The time-dependent degree of alignment measured, exhibits a periodic, gradually decreasing structure that deviates qualitatively from that expected for gas-phase dimers. Comparison to alignment dynamics calculated from the time-dependent rotational Schrödinger equation shows that the deviation is due to the alignment dependent interaction between the dimer and the droplet surface. This interaction confines the dimer to the tangential plane of the droplet surface at the point where it resides and is the reason that the observed alignment dynamics is also well described by a 2D quantum rotor model.

The phenuivirus Toscana virus makes an atypical use of vacuolar acidity to enter host cells - Koch, Jana; Xin, Qilin; Obr, Martin; Schäfer, Alicia; Rolfs, Nina; Anagho, Holda A.; Kudulyte, Aiste; Woltereck, Lea; Kummer, Susann; Campos, Joaquin; Uckeley, Zina M.; Bell-Sakyi, Lesley; et al. (PLoS Pathogens)
Toscana virus is a major cause of arboviral disease in humans in the Mediterranean basin during summer. However, early virus-host cell interactions and entry mechanisms remain poorly characterized. Investigating iPSC-derived human neurons and cell lines, we found that virus binding to the cell surface was specific, and 50% of bound virions were endocytosed within 10 min. Virions entered Rab5a+ early endosomes and, subsequently, Rab7a+ and LAMP-1+ late endosomal compartments. Penetration required intact late endosomes and occurred within 30 min following internalization. Virus entry relied on vacuolar acidification, with an optimal pH for viral membrane fusion at pH 5.5. The pH threshold increased to 5.8 with longer pre-exposure of virions to the slightly acidic pH in early endosomes. Strikingly, the particles remained infectious after entering late endosomes with a pH below the fusion threshold. Overall, our study establishes Toscana virus as a late-penetrating virus and reveals an atypical use of vacuolar acidity by this virus to enter host cells.

Antigravitropic PIN polarization maintains non-vertical growth in lateral roots - Roychoudhry, S; Sageman-Furnas, K; Wolverton, C; Grones, Peter; Tan, Shutang; Molnar, Gergely; De Angelis, M; Goodman, HL; Capstaff, N; JPB, Lloyd; Mullen, J; Hangarter, R; et al. (Nature Plants)
Lateral roots are typically maintained at non-vertical angles with respect to gravity. These gravitropic setpoint angles are intriguing because their maintenance requires that roots are able to effect growth response both with and against the gravity vector, a phenomenon previously attributed to gravitropism acting against an antigravitropic offset mechanism. Here we show how the components mediating gravitropism in the vertical primary root—PINs and phosphatases acting upon them—are reconfigured in their regulation such that lateral root growth at a range of angles can be maintained. We show that the ability of Arabidopsis lateral roots to bend both downward and upward requires the generation of auxin asymmetries and is driven by angle-dependent variation in downward gravitropic auxin flux acting against angle-independent upward, antigravitropic flux. Further, we demonstrate a symmetry in auxin distribution in lateral roots at gravitropic setpoint angle that can be traced back to a net, balanced polarization of PIN3 and PIN7 auxin transporters in the columella. These auxin fluxes are shifted by altering PIN protein phosphoregulation in the columella, either by introducing PIN3 phosphovariant versions or via manipulation of levels of the phosphatase subunit PP2A/RCN1. Finally, we show that auxin, in addition to driving lateral root directional growth, acts within the lateral root columella to induce more vertical growth by increasing RCN1 levels, causing a downward shift in PIN3 localization, thereby diminishing the magnitude of the upward, antigravitropic auxin flux.

Mitochondrial network adaptations of microglia reveal sex-specific stress response after injury and UCP2 knockout - Maes, Margaret E; Colombo, Gloria; Schoot Uiterkamp, Florianne E; Sternberg, Felix; Venturino, Alessandro; Pohl, Elena E.; Siegert, Sandra (iScience)
Mitochondrial networks remodel their connectivity, content, and subcellular localization to support optimized energy production in conditions of increased environmental or cellular stress. Microglia rely on mitochondria to respond to these stressors, however our knowledge about mitochondrial networks and their adaptations in microglia in vivo is limited. Here, we generate a mouse model that selectively labels mitochondria in microglia. We identify that mitochondrial networks are more fragmented with increased content and perinuclear localization in vitro vs. in vivo. Mitochondrial networks adapt similarly in microglia closest to the injury site after optic nerve crush. Preventing microglial UCP2 increase after injury by selective knockout induces cellular stress. This results in mitochondrial hyperfusion in male microglia, a phenotype absent in females due to circulating estrogens. Our results establish the foundation for mitochondrial network analysis of microglia in vivo, emphasizing the importance of mitochondrial-based sex effects of microglia in other pathologies.

Gaussian fluctuations in the equipartition principle for Wigner matrices - Cipolloni, Giorgio; Erdös, László; Henheik, Sven Joscha; Kolupaiev, Oleksii (Forum of Mathematics, Sigma)
The total energy of an eigenstate in a composite quantum system tends to be distributed equally among its constituents. We identify the quantum fluctuation around this equipartition principle in the simplest disordered quantum system consisting of linear combinations of Wigner matrices. As our main ingredient, we prove the Eigenstate Thermalisation Hypothesis and Gaussian fluctuation for general quadratic forms of the bulk eigenvectors of Wigner matrices with an arbitrary deformation.

Why extension-based proofs fail - Alistarh, Dan-Adrian; Aspnes, James; Ellen, Faith; Gelashvili, Rati; Zhu, Leqi (SIAM Journal on Computing)
We introduce extension-based proofs, a class of impossibility proofs that includes valency arguments. They are modelled as an interaction between a prover and a protocol. Using proofs based on combinatorial topology, it has been shown that it is impossible to deterministically solve -set agreement among processes or approximate agreement on a cycle of length 4 among processes in a wait-free manner in asynchronous models where processes communicate using objects that can be constructed from shared registers. However, it was unknown whether proofs based on simpler techniques were possible. We show that these impossibility results cannot be obtained by extension-based proofs in the iterated snapshot model and, hence, extension-based proofs are limited in power.

On angles in higher order Brillouin tessellations and related tilings in the plane - Edelsbrunner, Herbert; Garber, Alexey; Ghafari, Mohadese; Heiss, Teresa; Saghafian, Morteza (Discrete and Computational Geometry)
For a locally finite set in R2, the order-k Brillouin tessellations form an infinite sequence of convex face-to-face tilings of the plane. If the set is coarsely dense and generic, then the corresponding infinite sequences of minimum and maximum angles are both monotonic in k. As an example, a stationary Poisson point process in R2 is locally finite, coarsely dense, and generic with probability one. For such a set, the distributions of angles in the Voronoi tessellations, Delaunay mosaics, and Brillouin tessellations are independent of the order and can be derived from the formula for angles in order-1 Delaunay mosaics given by Miles (Math. Biosci. 6, 85–127 (1970)).

Self-organized and directed branching results in optimal coverage in developing dermal lymphatic networks - Ucar, Mehmet C; Hannezo, Edouard B; Tiilikainen, Emmi; Liaqat, Inam; Jakobsson, Emma; Nurmi, Harri; Vaahtomeri, Kari (Nature Communications)
Branching morphogenesis is a ubiquitous process that gives rise to high exchange surfaces in the vasculature and epithelial organs. Lymphatic capillaries form branched networks, which play a key role in the circulation of tissue fluid and immune cells. Although mouse models and correlative patient data indicate that the lymphatic capillary density directly correlates with functional output, i.e., tissue fluid drainage and trafficking efficiency of dendritic cells, the mechanisms ensuring efficient tissue coverage remain poorly understood. Here, we use the mouse ear pinna lymphatic vessel network as a model system and combine lineage-tracing, genetic perturbations, whole-organ reconstructions and theoretical modeling to show that the dermal lymphatic capillaries tile space in an optimal, space-filling manner. This coverage is achieved by two complementary mechanisms: initial tissue invasion provides a non-optimal global scaffold via self-organized branching morphogenesis, while VEGF-C dependent side-branching from existing capillaries rapidly optimizes local coverage by directionally targeting low-density regions. With these two ingredients, we show that a minimal biophysical model can reproduce quantitatively whole-network reconstructions, across development and perturbations. Our results show that lymphatic capillary networks can exploit local self-organizing mechanisms to achieve tissue-scale optimization.

Synchronization in collectively moving inanimate and living active matter - Riedl, Michael; Mayer, Isabelle D; Merrin, Jack; Sixt, Michael K; Hof, Björn (Nature Communications)
Whether one considers swarming insects, flocking birds, or bacterial colonies, collective motion arises from the coordination of individuals and entails the adjustment of their respective velocities. In particular, in close confinements, such as those encountered by dense cell populations during development or regeneration, collective migration can only arise coordinately. Yet, how individuals unify their velocities is often not understood. Focusing on a finite number of cells in circular confinements, we identify waves of polymerizing actin that function as a pacemaker governing the speed of individual cells. We show that the onset of collective motion coincides with the synchronization of the wave nucleation frequencies across the population. Employing a simpler and more readily accessible mechanical model system of active spheres, we identify the synchronization of the individuals’ internal oscillators as one of the essential requirements to reach the corresponding collective state. The mechanical ‘toy’ experiment illustrates that the global synchronous state is achieved by nearest neighbor coupling. We suggest by analogy that local coupling and the synchronization of actin waves are essential for the emergent, self-organized motion of cell collectives.

Creation rate of Dirac particles at a point source - Henheik, Sven Joscha; Tumulka, Roderich (Journal of Physics A: Mathematical and Theoretical)
Only recently has it been possible to construct a self-adjoint Hamiltonian that involves the creation of Dirac particles at a point source in 3d space. Its definition makes use of an interior-boundary condition. Here, we develop for this Hamiltonian a corresponding theory of the Bohmian configuration. That is, we (non-rigorously) construct a Markov jump process $(Q_t)_{t\in\mathbb{R}}$ in the configuration space of a variable number of particles that is $|ψ_t|^2$-distributed at every time t and follows Bohmian trajectories between the jumps. The jumps correspond to particle creation or annihilation events and occur either to or from a configuration with a particle located at the source. The process is the natural analog of Bell's jump process, and a central piece in its construction is the determination of the rate of particle creation. The construction requires an analysis of the asymptotic behavior of the Bohmian trajectories near the source. We find that the particle reaches the source with radial speed 0, but orbits around the source infinitely many times in finite time before absorption (or after emission).

Symbolic control for stochastic systems via finite parity games - Majumdar, Rupak; Mallik, Kaushik; Schmuck, Anne Kathrin; Soudjani, Sadegh (Nonlinear Analysis: Hybrid Systems)
We consider the problem of computing the maximal probability of satisfying an -regular specification for stochastic, continuous-state, nonlinear systems evolving in discrete time. The problem reduces, after automata-theoretic constructions, to finding the maximal probability of satisfying a parity condition on a (possibly hybrid) state space. While characterizing the exact satisfaction probability is open, we show that a lower bound on this probability can be obtained by (I) computing an under-approximation of the qualitative winning region, i.e., states from which the parity condition can be enforced almost surely, and (II) computing the maximal probability of reaching this qualitative winning region. The heart of our approach is a technique to symbolically compute the under-approximation of the qualitative winning region in step (I) via a finite-state abstraction of the original system as a -player parity game. Our abstraction procedure uses only the support of the probabilistic evolution; it does not use precise numerical transition probabilities. We prove that the winning set in the abstract -player game induces an under-approximation of the qualitative winning region in the original synthesis problem, along with a policy to solve it. By combining these contributions with (a) a symbolic fixpoint algorithm to solve -player games and (b) existing techniques for reachability policy synthesis in stochastic nonlinear systems, we get an abstraction-based algorithm for finding a lower bound on the maximal satisfaction probability. We have implemented the abstraction-based algorithm in Mascot-SDS, where we combined the outlined abstraction step with our tool Genie (Majumdar et al., 2023) that solves -player parity games (through a reduction to Rabin games) more efficiently than existing algorithms. We evaluated our implementation on the nonlinear model of a perturbed bistable switch from the literature. We show empirically that the lower bound on the winning region computed by our approach is precise, by comparing against an over-approximation of the qualitative winning region. Moreover, our implementation outperforms a recently proposed tool for solving this problem by a large margin.

Mechanistic insight on water dissociation on pristine low-index TiO2 surfaces from machine learning molecular dynamics simulations - Zeng, Zezhu; Wodaczek, Felix; Liu, Keyang; Stein, Frederick; Hutter, Jürg; Chen, Ji; Cheng, Bingqing (Nature Communications)
Water adsorption and dissociation processes on pristine low-index TiO2 interfaces are important but poorly understood outside the well-studied anatase (101) and rutile (110). To understand these, we construct three sets of machine learning potentials that are simultaneously applicable to various TiO2 surfaces, based on three density-functional-theory approximations. Here we show the water dissociation free energies on seven pristine TiO2 surfaces, and predict that anatase (100), anatase (110), rutile (001), and rutile (011) favor water dissociation, anatase (101) and rutile (100) have mostly molecular adsorption, while the simulations of rutile (110) sensitively depend on the slab thickness and molecular adsorption is preferred with thick slabs. Moreover, using an automated algorithm, we reveal that these surfaces follow different types of atomistic mechanisms for proton transfer and water dissociation: one-step, two-step, or both. These mechanisms can be rationalized based on the arrangements of water molecules on the different surfaces. Our finding thus demonstrates that the different pristine TiO2 surfaces react with water in distinct ways, and cannot be represented using just the low-energy anatase (101) and rutile (110) surfaces.

Extreme precipitation in tropical squall lines - Abramian, Sophie; Muller, Caroline J; Risi, Camille (Journal of Advances in Modeling Earth Systems)
Squall lines are substantially influenced by the interaction of low-level shear with cold pools associated with convective downdrafts. Beyond an optimal shear amplitude, squall lines tend to orient themselves at an angle with respect to the low-level shear. While the mechanisms behind squall line orientation seem to be increasingly well understood, uncertainties remain on the implications of this orientation. Roca and Fiolleau (2020, https://doi.org/10.1038/s43247-020-00015-4) show that long lived mesoscale convective systems, including squall lines, are disproportionately involved in rainfall extremes in the tropics. This article investigates the influence of the interaction between low-level shear and squall line outflow on squall line generated precipitation extrema in the tropics. Using a cloud resolving model, simulated squall lines in radiative convective equilibrium amid a shear-dominated regime (super optimal), a balanced regime (optimal), and an outflow dominated regime (suboptimal). Our results show that precipitation extremes in squall lines are 40% more intense in the case of optimal shear and remain 30% superior in the superoptimal regime relative to a disorganized case. With a theoretical scaling of precipitation extremes (C. Muller & Takayabu, 2020, https://doi.org/10.1088/1748-9326/ab7130), we show that the condensation rates control the amplification of precipitation extremes in tropical squall lines, mainly due to its change in vertical mass flux (dynamic component). The reduction of dilution by entrainment explains half of this change, consistent with Mulholland et al. (2021, https://doi.org/10.1175/jas-d-20-0299.1). The other half is explained by increased cloud-base velocity intensity in optimal and superoptimal squall lines.

A 3d‐4d‐5d high entropy alloy as a bifunctional oxygen catalyst for robust aqueous zinc–air batteries - He, Ren; Yang, Linlin; Zhang, Yu; Jiang, Daochuan; Lee, Seungho; Horta, Sharona; Liang, Zhifu; Lu, Xuan; Ostovari Moghaddam, Ahmad; Li, Junshan; Ibáñez, Maria; Xu, Ying; et al. (Advanced Materials)
High entropy alloys (HEAs) are highly suitable candidate catalysts for oxygen evolution and reduction reactions (OER/ORR) as they offer numerous parameters for optimizing the electronic structure and catalytic sites. Herein, FeCoNiMoW HEA nanoparticles are synthesized using a solution‐based low‐temperature approach. Such FeCoNiMoW nanoparticles show high entropy properties, subtle lattice distortions, and modulated electronic structure, leading to superior OER performance with an overpotential of 233 mV at 10 mA cm −2 and 276 mV at 100 mA cm −2 . Density functional theory calculations reveal the electronic structures of the FeCoNiMoW active sites with an optimized d‐band center position that enables suitable adsorption of OOH* intermediates and reduces the Gibbs free energy barrier in the OER process. Aqueous zinc–air batteries (ZABs) based on this HEA demonstrate a high open circuit potential of 1.59 V, a peak power density of 116.9 mW cm −2 , a specific capacity of 857 mAh g Zn −1 , and excellent stability for over 660 h of continuous charge–discharge cycles. Flexible and solid ZABs are also assembled and tested, displaying excellent charge–discharge performance at different bending angles. This work shows the significance of 4d/5d metal‐modulated electronic structure and optimized adsorption ability to improve the performance of OER/ORR, ZABs, and beyond.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

A layered Bi2Te3@PPy cathode for aqueous zinc ion batteries: Mechanism and application in printed flexible batteries - Zeng, Guifang; Sun, Qing; Horta, Sharona; Wang, Shang; Lu, Xuan; Zhang, Chaoyue; Li, Jing; Li, Junshan; Ci, Lijie; Tian, Yanhong; Ibáñez, Maria; Cabot, Andreu (Advanced Materials)
Low‐cost, safe, and environmental‐friendly rechargeable aqueous zinc‐ion batteries (ZIBs) are promising as next‐generation energy storage devices for wearable electronics among other applications. However, sluggish ionic transport kinetics and the unstable electrode structure during ionic insertion/extraction hampers their deployment. Herein, we propose a new cathode material based on a layered metal chalcogenide (LMC), bismuth telluride (Bi 2 Te 3 ), coated with polypyrrole (PPy). Taking advantage of the PPy coating, the Bi 2 Te 3 @PPy composite presents strong ionic absorption affinity, high oxidation resistance, and high structural stability. The ZIBs based on Bi 2 Te 3 @PPy cathodes exhibit high capacities and ultra‐long lifespans of over 5000 cycles. They also present outstanding stability even under bending. In addition, we analyze here the reaction mechanism using in situ X‐ray diffraction, X‐ray photoelectron spectroscopy, and computational tools and demonstrate that, in the aqueous system, Zn 2+ is not inserted into the cathode as previously assumed. In contrast, proton charge storage dominates the process. Overall, this work not only shows the great potential of LMCs as ZIBs cathode materials and the advantages of PPy coating, but also clarifies the charge/discharge mechanism in rechargeable ZIBs based on LMCs.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Chromosomal inversion polymorphisms are widespread across the species ranges of rough periwinkles (Littorina saxatilis and L. arcana) - Reeve, James; Butlin, Roger K.; Koch, Eva L.; Stankowski, Sean; Faria, Rui (Molecular Ecology)
Inversions are thought to play a key role in adaptation and speciation, suppressing recombination between diverging populations. Genes influencing adaptive traits cluster in inversions, and changes in inversion frequencies are associated with environmental differences. However, in many organisms, it is unclear if inversions are geographically and taxonomically widespread. The intertidal snail, Littorina saxatilis, is one such example. Strong associations between putative polymorphic inversions and phenotypic differences have been demonstrated between two ecotypes of L. saxatilis in Sweden and inferred elsewhere, but no direct evidence for inversion polymorphism currently exists across the species range. Using whole genome data from 107 snails, most inversion polymorphisms were found to be widespread across the species range. The frequencies of some inversion arrangements were significantly different among ecotypes, suggesting a parallel adaptive role. Many inversions were also polymorphic in the sister species, L. arcana, hinting at an ancient origin.

Tempering expectations: Considerations on the current state of stem cells therapy for autism treatment - Narzisi, Antonio; Halladay, Alycia; Masi, Gabriele; Novarino, Gaia; Lord, Catherine (Frontiers in Psychiatry)

Length spectrum rigidity for piecewise analytic Bunimovich billiards - Chen, Jianyu; Kaloshin, Vadim; Zhang, Hong Kun (Communications in Mathematical Physics)
In the paper, we establish Squash Rigidity Theorem—the dynamical spectral rigidity for piecewise analytic Bunimovich squash-type stadia whose convex arcs are homothetic. We also establish Stadium Rigidity Theorem—the dynamical spectral rigidity for piecewise analytic Bunimovich stadia whose flat boundaries are a priori fixed. In addition, for smooth Bunimovich squash-type stadia we compute the Lyapunov exponents along the maximal period two orbit, as well as the value of the Peierls’ Barrier function from the maximal marked length spectrum associated to the rotation number 2n/4n+1.

Optimal embedded and enclosing isosceles triangles - Ambrus, Áron; Csikós, Mónika; Kiss, Gergely; Pach, János; Somlai, Gábor (International Journal of Foundations of Computer Science)
Given a triangle Δ, we study the problem of determining the smallest enclosing and largest embedded isosceles triangles of Δ with respect to area and perimeter. This problem was initially posed by Nandakumar [17, 22] and was first studied by Kiss, Pach, and Somlai [13], who showed that if Δ′ is the smallest area isosceles triangle containing Δ, then Δ′ and Δ share a side and an angle. In the present paper, we prove that for any triangle Δ, every maximum area isosceles triangle embedded in Δ and every maximum perimeter isosceles triangle embedded in Δ shares a side and an angle with Δ. Somewhat surprisingly, the case of minimum perimeter enclosing triangles is different: there are infinite families of triangles Δ whose minimum perimeter isosceles containers do not share a side and an angle with Δ.

Advancing microbiome research with machine learning: Key findings from the ML4Microbiome COST action - D’Elia, Domenica; Truu, Jaak; Lahti, Leo; Berland, Magali; Papoutsoglou, Georgios; Ceci, Michelangelo; Zomer, Aldert; Lopes, Marta B.; Ibrahimi, Eliana; Gruca, Aleksandra; Nechyporenko, Alina; Frohme, Marcus; et al. (Frontiers in Microbiology)
The rapid development of machine learning (ML) techniques has opened up the data-dense field of microbiome research for novel therapeutic, diagnostic, and prognostic applications targeting a wide range of disorders, which could substantially improve healthcare practices in the era of precision medicine. However, several challenges must be addressed to exploit the benefits of ML in this field fully. In particular, there is a need to establish “gold standard” protocols for conducting ML analysis experiments and improve interactions between microbiome researchers and ML experts. The Machine Learning Techniques in Human Microbiome Studies (ML4Microbiome) COST Action CA18131 is a European network established in 2019 to promote collaboration between discovery-oriented microbiome researchers and data-driven ML experts to optimize and standardize ML approaches for microbiome analysis. This perspective paper presents the key achievements of ML4Microbiome, which include identifying predictive and discriminatory ‘omics’ features, improving repeatability and comparability, developing automation procedures, and defining priority areas for the novel development of ML methods targeting the microbiome. The insights gained from ML4Microbiome will help to maximize the potential of ML in microbiome research and pave the way for new and improved healthcare practices.

Recursive greedy initialization of the quantum approximate optimization algorithm with guaranteed improvement - Sack, Stefan; Medina Ramos, Raimel A; Kueng, Richard; Serbyn, Maksym (Physical Review A)
The quantum approximate optimization algorithm (QAOA) is a variational quantum algorithm, where a quantum computer implements a variational ansatz consisting of p layers of alternating unitary operators and a classical computer is used to optimize the variational parameters. For a random initialization, the optimization typically leads to local minima with poor performance, motivating the search for initialization strategies of QAOA variational parameters. Although numerous heuristic initializations exist, an analytical understanding and performance guarantees for large p remain evasive.We introduce a greedy initialization of QAOA which guarantees improving performance with an increasing number of layers. Our main result is an analytic construction of 2p + 1 transition states—saddle points with a unique negative curvature direction—for QAOA with p + 1 layers that use the local minimum of QAOA with p layers. Transition states connect to new local minima, which are guaranteed to lower the energy compared to the minimum found for p layers. We use the GREEDY procedure to navigate the exponentially increasing with p number of local minima resulting from the recursive application of our analytic construction. The performance of the GREEDY procedure matches available initialization strategies while providing a guarantee for the minimal energy to decrease with an increasing number of layers p.

Coboundary expansion, equivariant overlap, and crossing numbers of simplicial complexes - Wagner, Uli; Wild, Pascal (Israel Journal of Mathematics)
We prove the following quantitative Borsuk–Ulam-type result (an equivariant analogue of Gromov’s Topological Overlap Theorem): Let X be a free ℤ/2-complex of dimension d with coboundary expansion at least ηk in dimension 0 ≤ k < d. Then for every equivariant map F: X →ℤ/2 ℝd, the fraction of d-simplices σ of X with 0 ∈ F (σ) is at least 2−d Π d−1k=0ηk. As an application, we show that for every sufficiently thick d-dimensional spherical building Y and every map f: Y → ℝ2d, we have f(σ) ∩ f(τ) ≠ ∅ for a constant fraction μd > 0 of pairs {σ, τ} of d-simplices of Y. In particular, such complexes are non-embeddable into ℝ2d, which proves a conjecture of Tancer and Vorwerk for sufficiently thick spherical buildings. We complement these results by upper bounds on the coboundary expansion of two families of simplicial complexes; this indicates some limitations to the bounds one can obtain by straighforward applications of the quantitative Borsuk–Ulam theorem. Specifically, we prove • an upper bound of (d + 1)/2d on the normalized (d − 1)-th coboundary expansion constant of complete (d + 1)-partite d-dimensional complexes (under a mild divisibility assumption on the sizes of the parts); and • an upper bound of (d + 1)/2d + ε on the normalized (d − 1)-th coboundary expansion of the d-dimensional spherical building associated with GLd+2(Fq) for any ε > 0 and sufficiently large q. This disproves, in a rather strong sense, a conjecture of Lubotzky, Meshulam and Mozes.

New fluorescent auxin derivatives: anti-auxin activity and accumulation patterns in Arabidopsis thaliana - Bieleszová, Kristýna; Hladík, Pavel; Kubala, Martin; Napier, Richard; Brunoni, Federica; Gelová, Zuzana; Fiedler, Lukas; Kulich, Ivan; Strnad, Miroslav; Doležal, Karel; Novák, Ondřej; Friml, Jiří; et al. (Plant Growth Regulation)
Auxin belongs among major phytohormones and governs multiple aspects of plant growth and development. The establishment of auxin concentration gradients, determines, among other processes, plant organ positioning and growth responses to environmental stimuli. Herein we report the synthesis of new NBD- or DNS-labelled IAA derivatives and the elucidation of their biological activity, fluorescence properties and subcellular accumulation patterns in planta. These novel compounds did not show auxin-like activity, but instead antagonized physiological auxin effects. The DNS-labelled derivatives FL5 and FL6 showed strong anti-auxin activity in roots and hypocotyls, which also occurred at the level of gene transcription as confirmed by quantitative PCR analysis. The auxin antagonism of our derivatives was further demonstrated in vitro using an SPR-based binding assay. The NBD-labelled compound FL4 with the best fluorescence properties proved to be unsuitable to study auxin accumulation patterns in planta. On the other hand, the strongest anti-auxin activity possessing compounds FL5 and FL6 could be useful to study binding mechanisms to auxin receptors and for manipulations of auxin-regulated processes.

Improving variational quantum algorithms: Innovative initialization techniques and extensions to qudit systems - Sack, Stefan

Protocol for sorting cells from mouse brains labeled with mosaic analysis with double markers by flow cytometry - Amberg, Nicole; Cheung, Giselle T; Hippenmeyer, Simon (STAR Protocols)
Mosaic analysis with double markers (MADM) technology enables the generation of genetic mosaic tissue in mice and high-resolution phenotyping at the individual cell level. Here, we present a protocol for isolating MADM-labeled cells with high yield for downstream molecular analyses using fluorescence-activated cell sorting (FACS). We describe steps for generating MADM-labeled mice, perfusion, single-cell suspension, and debris removal. We then detail procedures for cell sorting by FACS and downstream analysis. This protocol is suitable for embryonic to adult mice. For complete details on the use and execution of this protocol, please refer to Contreras et al. (2021).1
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Neuroscience

Delayed blow-up and enhanced diffusion by transport noise for systems of reaction-diffusion equations - Agresti, Antonio (Stochastics and Partial Differential Equations: Analysis and Computations)
This paper is concerned with the problem of regularization by noise of systems of reaction–diffusion equations with mass control. It is known that strong solutions to such systems of PDEs may blow-up in finite time. Moreover, for many systems of practical interest, establishing whether the blow-up occurs or not is an open question. Here we prove that a suitable multiplicative noise of transport type has a regularizing effect. More precisely, for both a sufficiently noise intensity and a high spectrum, the blow-up of strong solutions is delayed up to an arbitrary large time. Global existence is shown for the case of exponentially decreasing mass. The proofs combine and extend recent developments in regularization by noise and in the Lp(Lq)-approach to stochastic PDEs, highlighting new connections between the two areas.

Multiple packing: Lower bounds via error exponents - Zhang, Yihan; Vatedka, Shashank (IEEE Transactions on Information Theory)
We derive lower bounds on the maximal rates for multiple packings in high-dimensional Euclidean spaces. For any N > 0 and L ∈ Z ≥2 , a multiple packing is a set C of points in R n such that any point in R n lies in the intersection of at most L - 1 balls of radius √ nN around points in C . This is a natural generalization of the sphere packing problem. We study the multiple packing problem for both bounded point sets whose points have norm at most √ nP for some constant P > 0, and unbounded point sets whose points are allowed to be anywhere in R n . Given a well-known connection with coding theory, multiple packings can be viewed as the Euclidean analog of list-decodable codes, which are well-studied over finite fields. We derive the best known lower bounds on the optimal multiple packing density. This is accomplished by establishing an inequality which relates the list-decoding error exponent for additive white Gaussian noise channels, a quantity of average-case nature, to the list-decoding radius, a quantity of worst-case nature. We also derive novel bounds on the list-decoding error exponent for infinite constellations and closed-form expressions for the list-decoding error exponents for the power-constrained AWGN channel, which may be of independent interest beyond multiple packing.

(Verifiable) delay functions from Lucas sequences - Hoffmann, Charlotte; Hubáček, Pavel; Kamath, Chethan; Krňák, Tomáš (21st International Conference on Theory of Cryptography)
Lucas sequences are constant-recursive integer sequences with a long history of applications in cryptography, both in the design of cryptographic schemes and cryptanalysis. In this work, we study the sequential hardness of computing Lucas sequences over an RSA modulus. First, we show that modular Lucas sequences are at least as sequentially hard as the classical delay function given by iterated modular squaring proposed by Rivest, Shamir, and Wagner (MIT Tech. Rep. 1996) in the context of time-lock puzzles. Moreover, there is no obvious reduction in the other direction, which suggests that the assumption of sequential hardness of modular Lucas sequences is strictly weaker than that of iterated modular squaring. In other words, the sequential hardness of modular Lucas sequences might hold even in the case of an algorithmic improvement violating the sequential hardness of iterated modular squaring. Second, we demonstrate the feasibility of constructing practically-efficient verifiable delay functions based on the sequential hardness of modular Lucas sequences. Our construction builds on the work of Pietrzak (ITCS 2019) by leveraging the intrinsic connection between the problem of computing modular Lucas sequences and exponentiation in an appropriate extension field.

On the cost of post-compromise security in concurrent Continuous Group-Key Agreement - Auerbach, Benedikt; Cueto Noval, Miguel; Pascual Perez, Guillermo; Pietrzak, Krzysztof Z (21st International Conference on Theory of Cryptography)
Continuous Group-Key Agreement (CGKA) allows a group of users to maintain a shared key. It is the fundamental cryptographic primitive underlying group messaging schemes and related protocols, most notably TreeKEM, the underlying key agreement protocol of the Messaging Layer Security (MLS) protocol, a standard for group messaging by the IETF. CKGA works in an asynchronous setting where parties only occasionally must come online, and their messages are relayed by an untrusted server. The most expensive operation provided by CKGA is that which allows for a user to refresh their key material in order to achieve forward secrecy (old messages are secure when a user is compromised) and post-compromise security (users can heal from compromise). One caveat of early CGKA protocols is that these update operations had to be performed sequentially, with any user wanting to update their key material having had to receive and process all previous updates. Late versions of TreeKEM do allow for concurrent updates at the cost of a communication overhead per update message that is linear in the number of updating parties. This was shown to be indeed necessary when achieving PCS in just two rounds of communication by [Bienstock et al. TCC’20]. The recently proposed protocol CoCoA [Alwen et al. Eurocrypt’22], however, shows that this overhead can be reduced if PCS requirements are relaxed, and only a logarithmic number of rounds is required. The natural question, thus, is whether CoCoA is optimal in this setting. In this work we answer this question, providing a lower bound on the cost (concretely, the amount of data to be uploaded to the server) for CGKA protocols that heal in an arbitrary k number of rounds, that shows that CoCoA is very close to optimal. Additionally, we extend CoCoA to heal in an arbitrary number of rounds, and propose a modification of it, with a reduced communication cost for certain k. We prove our bound in a combinatorial setting where the state of the protocol progresses in rounds, and the state of the protocol in each round is captured by a set system, each set specifying a set of users who share a secret key. We show this combinatorial model is equivalent to a symbolic model capturing building blocks including PRFs and public-key encryption, related to the one used by Bienstock et al. Our lower bound is of order k•n1+1/(k-1)/log(k), where 2≤k≤log(n) is the number of updates per user the protocol requires to heal. This generalizes the n2 bound for k=2 from Bienstock et al.. This bound almost matches the k⋅n1+2/(k-1) or k2⋅n1+1/(k-1) efficiency we get for the variants of the CoCoA protocol also introduced in this paper.

Generic-group lower bounds via reductions between geometric-search problems: With and without preprocessing - Auerbach, Benedikt; Hoffmann, Charlotte; Pascual Perez, Guillermo (21st International Conference on Theory of Cryptography)
The generic-group model (GGM) aims to capture algorithms working over groups of prime order that only rely on the group operation, but do not exploit any additional structure given by the concrete implementation of the group. In it, it is possible to prove information-theoretic lower bounds on the hardness of problems like the discrete logarithm (DL) or computational Diffie-Hellman (CDH). Thus, since its introduction, it has served as a valuable tool to assess the concrete security provided by cryptographic schemes based on such problems. A work on the related algebraic-group model (AGM) introduced a method, used by many subsequent works, to adapt GGM lower bounds for one problem to another, by means of conceptually simple reductions. In this work, we propose an alternative approach to extend GGM bounds from one problem to another. Following an idea by Yun [EC15], we show that, in the GGM, the security of a large class of problems can be reduced to that of geometric search-problems. By reducing the security of the resulting geometric-search problems to variants of the search-by-hypersurface problem, for which information theoretic lower bounds exist, we give alternative proofs of several results that used the AGM approach. The main advantage of our approach is that our reduction from geometric search-problems works, as well, for the GGM with preprocessing (more precisely the bit-fixing GGM introduced by Coretti, Dodis and Guo [Crypto18]). As a consequence, this opens up the possibility of transferring preprocessing GGM bounds from one problem to another, also by means of simple reductions. Concretely, we prove novel preprocessing bounds on the hardness of the d-strong discrete logarithm, the d-strong Diffie-Hellman inversion, and multi-instance CDH problems, as well as a large class of Uber assumptions. Additionally, our approach applies to Shoup’s GGM without additional restrictions on the query behavior of the adversary, while the recent works of Zhang, Zhou, and Katz [AC22] and Zhandry [Crypto22] highlight that this is not the case for the AGM approach.

Boundary multifractality in the spin quantum Hall symmetry class with interaction - Babkin, Serafim; Burmistrov, I (Physical Review B)
Generalized multifractality characterizes system size dependence of pure scaling local observables at Anderson transitions in all 10 symmetry classes of disordered systems. Recently, the concept of generalized multifractality has been extended to boundaries of critical disordered noninteracting systems. Here we study the generalized boundary multifractality in the presence of electron-electron interaction, focusing on the spin quantum Hall symmetry class (class C). Employing the two-loop renormalization group analysis within the Finkel'stein nonlinear sigma model, we compute the anomalous dimensions of the pure scaling operators located at the boundary of the system. We find that generalized boundary multifractal exponents are twice larger than their bulk counterparts. Exact symmetry relations between generalized boundary multifractal exponents in the case of noninteracting systems are explicitly broken by the interaction.

Reply to: Revisiting the use of structural similarity index in Hi-C - Ing-Simmons, Elizabeth; Machnik, Nick N; Vaquerizas, Juan M. (Nature Genetics)

Towards practical metal–oxygen batteries: General discussion - Archer, Lynden A.; Bruce, Peter G.; Calvo, Ernesto J.; Dewar, Daniel; Ellison, James H. J.; Freunberger, Stefan Alexander; Gao, Xiangwen; Hardwick, Laurence J.; Horwitz, Gabriela; Janek, Jürgen; Johnson, Lee R.; Jordan, Jack W.; et al. (Faraday Discussions)
Keywords: Physical and Theoretical Chemistry

Materials for stable metal–oxygen battery cathodes: general discussion - Attard, Gary A.; Calvo, Ernesto J.; Curtiss, Larry A.; Dewar, Daniel; Ellison, James H. J.; Gao, Xiangwen; Grey, Clare P.; Hardwick, Laurence J.; Horwitz, Gabriela; Janek, Juergen; Johnson, Lee R.; Jordan, Jack W.; et al. (Faraday Discussions)
Keywords: Physical and Theoretical Chemistry

Sensing their plasma membrane curvature allows migrating cells to circumvent obstacles - Sitarska, Ewa; Almeida, Silvia Dias; Beckwith, Marianne Sandvold; Stopp, Julian A; Czuchnowski, Jakub; Siggel, Marc; Roessner, Rita; Tschanz, Aline; Ejsing, Christer; Schwab, Yannick; Kosinski, Jan; Sixt, Michael K; et al. (Nature Communications)
To navigate through diverse tissues, migrating cells must balance persistent self-propelled motion with adaptive behaviors to circumvent obstacles. We identify a curvature-sensing mechanism underlying obstacle evasion in immune-like cells. Specifically, we propose that actin polymerization at the advancing edge of migrating cells is inhibited by the curvature-sensitive BAR domain protein Snx33 in regions with inward plasma membrane curvature. The genetic perturbation of this machinery reduces the cells’ capacity to evade obstructions combined with faster and more persistent cell migration in obstacle-free environments. Our results show how cells can read out their surface topography and utilize actin and plasma membrane biophysics to interpret their environment, allowing them to adaptively decide if they should move ahead or turn away. On the basis of our findings, we propose that the natural diversity of BAR domain proteins may allow cells to tune their curvature sensing machinery to match the shape characteristics in their environment.

CCR7 acts as both a sensor and a sink for CCL19 to coordinate collective leukocyte migration - Alanko, Jonna H; Ucar, Mehmet C; Canigova, Nikola; Stopp, Julian A; Schwarz, Jan; Merrin, Jack; Hannezo, Edouard B; Sixt, Michael K (Science Immunology)
Immune responses rely on the rapid and coordinated migration of leukocytes. Whereas it is well established that single-cell migration is often guided by gradients of chemokines and other chemoattractants, it remains poorly understood how these gradients are generated, maintained, and modulated. By combining experimental data with theory on leukocyte chemotaxis guided by the G protein–coupled receptor (GPCR) CCR7, we demonstrate that in addition to its role as the sensory receptor that steers migration, CCR7 also acts as a generator and a modulator of chemotactic gradients. Upon exposure to the CCR7 ligand CCL19, dendritic cells (DCs) effectively internalize the receptor and ligand as part of the canonical GPCR desensitization response. We show that CCR7 internalization also acts as an effective sink for the chemoattractant, dynamically shaping the spatiotemporal distribution of the chemokine. This mechanism drives complex collective migration patterns, enabling DCs to create or sharpen chemotactic gradients. We further show that these self-generated gradients can sustain the long-range guidance of DCs, adapt collective migration patterns to the size and geometry of the environment, and provide a guidance cue for other comigrating cells. Such a dual role of CCR7 as a GPCR that both senses and consumes its ligand can thus provide a novel mode of cellular self-organization.
Keywords: General Medicine; Immunology

Neutrophils on the hunt: Migratory strategies employed by neutrophils to fulfill their effector function - Stopp, Julian A

Investigating inbreeding depression and the self-incompatibility locus of Antirrhinum majus - Arathoon, Louise S
For self-incompatibility (SI) to be stable in a population, theory predicts that sufficient inbreeding depression (ID) is required: the fitness of offspring from self-mated individuals must be low enough to prevent the spread of self-compatibility (SC). Reviews of natural plant populations have supported this theory, with SI species generally showing high levels of ID. However, there is thought to be an under-sampling of self-incompatible taxa in the current literature. In this thesis, I study inbreeding depression in the SI plant species Antirrhinum majus using both greenhouse crosses and a large collected field dataset. Additionally, the gametophytic S-locus of A. majus is highly heterozygous and polymorphic, thus making assembly and discovery of S-alleles very difficult. Here, 206 new alleles of the male component SLFs are presented, along with a phylogeny showing the high conservation with alleles from another Antirrhinum species. Lastly, selected sites within the protein structure of SLFs are investigated, with one site in particular highlighted as potentially being involved in the SI recognition mechanism.

Quantitative convergence of a discretization of dynamic optimal transport using the dual formulation - Ishida, Sadashige; Lavenant, Hugo (arXiv)
We present a discretization of the dynamic optimal transport problem for which we can obtain the convergence rate for the value of the transport cost to its continuous value when the temporal and spatial stepsize vanish. This convergence result does not require any regularity assumption on the measures, though experiments suggest that the rate is not sharp. Via an analysis of the duality gap we also obtain the convergence rates for the gradient of the optimal potentials and the velocity field under mild regularity assumptions. To obtain such rates we discretize the dual formulation of the dynamic optimal transport problem and use the mature literature related to the error due to discretizing the Hamilton-Jacobi equation.
Keywords: Optimal transport; Hamilton-Jacobi equation; convex optimization

Machine learning and phylogenetic analysis allow for predicting antibiotic resistance in M. tuberculosis - Yurtseven, Alper; Buyanova, Sofia; Agrawal, Amay Ajaykumar A.; Bochkareva, Olga; Kalinina, Olga V V. (BMC Microbiology)
Background: Antimicrobial resistance (AMR) poses a significant global health threat, and an accurate prediction of bacterial resistance patterns is critical for effective treatment and control strategies. In recent years, machine learning (ML) approaches have emerged as powerful tools for analyzing large-scale bacterial AMR data. However, ML methods often ignore evolutionary relationships among bacterial strains, which can greatly impact performance of the ML methods, especially if resistance-associated features are attempted to be detected. Genome-wide association studies (GWAS) methods like linear mixed models accounts for the evolutionary relationships in bacteria, but they uncover only highly significant variants which have already been reported in literature. Results: In this work, we introduce a novel phylogeny-related parallelism score (PRPS), which measures whether a certain feature is correlated with the population structure of a set of samples. We demonstrate that PRPS can be used, in combination with SVM- and random forest-based models, to reduce the number of features in the analysis, while simultaneously increasing models’ performance. We applied our pipeline to publicly available AMR data from PATRIC database for Mycobacterium tuberculosis against six common antibiotics. Conclusions: Using our pipeline, we re-discovered known resistance-associated mutations as well as new candidate mutations which can be related to resistance and not previously reported in the literature. We demonstrated that taking into account phylogenetic relationships not only improves the model performance, but also yields more biologically relevant predicted most contributing resistance markers.

Binary decision diagrams on modern hardware - Pastva, Samuel; Henzinger, Thomas A (Proceedings of the 23rd Conference on Formal Methods in Computer-Aided Design)
Binary decision diagrams (BDDs) are one of the fundamental data structures in formal methods and computer science in general. However, the performance of BDD-based algorithms greatly depends on memory latency due to the reliance on large hash tables and thus, by extension, on the speed of random memory access. This hinders the full utilisation of resources available on modern CPUs, since the absolute memory latency has not improved significantly for at least a decade. In this paper, we explore several implementation techniques that improve the performance of BDD manipulation either through enhanced memory locality or by partially eliminating random memory access. On a benchmark suite of 600+ BDDs derived from real-world applications, we demonstrate runtime that is comparable or better than parallelising the same operations on eight CPU cores.

Equidistribution of primitive lattices in ℝn - Horesh, Tal; Karasik, Yakov (Quarterly Journal of Mathematics)
We count primitive lattices of rank d inside Zn as their covolume tends to infinity, with respect to certain parameters of such lattices. These parameters include, for example, the subspace that a lattice spans, namely its projection to the Grassmannian; its homothety class and its equivalence class modulo rescaling and rotation, often referred to as a shape. We add to a prior work of Schmidt by allowing sets in the spaces of parameters that are general enough to conclude the joint equidistribution of these parameters. In addition to the primitive d-lattices Λ themselves, we also consider their orthogonal complements in Zn⁠, A1⁠, and show that the equidistribution occurs jointly for Λ and A1⁠. Finally, our asymptotic formulas for the number of primitive lattices include an explicit bound on the error term.

Nanostructured Li₂S cathodes for silicon-sulfur batteries - Mollania, Hamid; Zhang, Chaoqi; Du, Ruifeng; Qi, Xueqiang; Li, Junshan; Horta, Sharona; Ibáñez, Maria; Keller, Caroline; Chenevier, Pascale; Oloomi-Buygi, Majid; Cabot, Andreu (ACS Applied Materials and Interfaces)
Lithium–sulfur batteries are regarded as an advantageous option for meeting the growing demand for high-energy-density storage, but their commercialization relies on solving the current limitations of both sulfur cathodes and lithium metal anodes. In this scenario, the implementation of lithium sulfide (Li2S) cathodes compatible with alternative anode materials such as silicon has the potential to alleviate the safety concerns associated with lithium metal. In this direction, here, we report a sulfur cathode based on Li2S nanocrystals grown on a catalytic host consisting of CoFeP nanoparticles supported on tubular carbon nitride. Nanosized Li2S is incorporated into the host by a scalable liquid infiltration–evaporation method. Theoretical calculations and experimental results demonstrate that the CoFeP–CN composite can boost the polysulfide adsorption/conversion reaction kinetics and strongly reduce the initial overpotential activation barrier by stretching the Li–S bonds of Li2S. Besides, the ultrasmall size of the Li2S particles in the Li2S–CoFeP–CN composite cathode facilitates the initial activation. Overall, the Li2S–CoFeP–CN electrodes exhibit a low activation barrier of 2.56 V, a high initial capacity of 991 mA h gLi2S–1, and outstanding cyclability with a small fading rate of 0.029% per cycle over 800 cycles. Moreover, Si/Li2S full cells are assembled using the nanostructured Li2S–CoFeP–CN cathode and a prelithiated anode based on graphite-supported silicon nanowires. These Si/Li2S cells demonstrate high initial discharge capacities above 900 mA h gLi2S–1 and good cyclability with a capacity fading rate of 0.28% per cycle over 150 cycles.

Exponential decay of the number of excitations in the weakly interacting Bose gas - Mitrouskas, David Johannes; Pickl, Peter (Journal of Mathematical Physics)
We consider N trapped bosons in the mean-field limit with coupling constant λN = 1/(N − 1). The ground state of such systems exhibits Bose–Einstein condensation. We prove that the probability of finding ℓ particles outside the condensate wave function decays exponentially in ℓ.

Generalizing shallow water simulations with dispersive surface waves - Jeschke, Stefan; Wojtan, Christopher J (ACM Transactions on Graphics)
This paper introduces a novel method for simulating large bodies of water as a height field. At the start of each time step, we partition the waves into a bulk flow (which approximately satisfies the assumptions of the shallow water equations) and surface waves (which approximately satisfy the assumptions of Airy wave theory). We then solve the two wave regimes separately using appropriate state-of-the-art techniques, and re-combine the resulting wave velocities at the end of each step. This strategy leads to the first heightfield wave model capable of simulating complex interactions between both deep and shallow water effects, like the waves from a boat wake sloshing up onto a beach, or a dam break producing wave interference patterns and eddies. We also analyze the numerical dispersion created by our method and derive an exact correction factor for waves at a constant water depth, giving us a numerically perfect re-creation of theoretical water wave dispersion patterns.

A computational toolbox for the assembly yield of complex and heterogeneous structures - Curatolo, Agnese I.; Kimchi, Ofer; Goodrich, Carl Peter; Krueger, Ryan K.; Brenner, Michael P. (Nature Communications)
The self-assembly of complex structures from a set of non-identical building blocks is a hallmark of soft matter and biological systems, including protein complexes, colloidal clusters, and DNA-based assemblies. Predicting the dependence of the equilibrium assembly yield on the concentrations and interaction energies of building blocks is highly challenging, owing to the difficulty of computing the entropic contributions to the free energy of the many structures that compete with the ground state configuration. While these calculations yield well known results for spherically symmetric building blocks, they do not hold when the building blocks have internal rotational degrees of freedom. Here we present an approach for solving this problem that works with arbitrary building blocks, including proteins with known structure and complex colloidal building blocks. Our algorithm combines classical statistical mechanics with recently developed computational tools for automatic differentiation. Automatic differentiation allows efficient evaluation of equilibrium averages over configurations that would otherwise be intractable. We demonstrate the validity of our framework by comparison to molecular dynamics simulations of simple examples, and apply it to calculate the yield curves for known protein complexes and for the assembly of colloidal shells.

Auxin research: Creating tools for a greener future - Del Bianco, Marta; Friml, Jiří; Strader, Lucia; Kepinski, Stefan (Journal of Experimental Botany)
Amid the delays due to the global pandemic, in early October 2022, the auxin community gathered in the idyllic peninsula of Cavtat, Croatia. More than 170 scientists from across the world converged to discuss the latest advancements in fundamental and applied research in the field. The topics, from signalling and transport to plant architecture and response to the environment, show how auxin research must bridge from the molecular realm to macroscopic developmental responses. This is mirrored in this collection of reviews, contributed by participants of the Auxin 2022 meeting.

Token swapping on trees - Biniaz, Ahmad; Jain, Kshitij; Lubiw, Anna; Masárová, Zuzana; Miltzow, Tillmann; Mondal, Debajyoti; Naredla, Anurag Murty; Tkadlec, Josef; Turcotte, Alexi (Discrete Mathematics and Theoretical Computer Science)
The input to the token swapping problem is a graph with vertices v1, v2, . . . , vn, and n tokens with labels 1,2, . . . , n, one on each vertex. The goal is to get token i to vertex vi for all i= 1, . . . , n using a minimum number of swaps, where a swap exchanges the tokens on the endpoints of an edge.Token swapping on a tree, also known as “sorting with a transposition tree,” is not known to be in P nor NP-complete. We present some partial results: 1. An optimum swap sequence may need to perform a swap on a leaf vertex that has the correct token (a “happy leaf”), disproving a conjecture of Vaughan. 2. Any algorithm that fixes happy leaves—as all known approximation algorithms for the problem do—has approximation factor at least 4/3. Furthermore, the two best-known 2-approximation algorithms have approximation factor exactly 2. 3. A generalized problem—weighted coloured token swapping—is NP-complete on trees, but solvable in polynomial time on paths and stars. In this version, tokens and vertices have colours, and colours have weights. The goal is to get every token to a vertex of the same colour, and the cost of a swap is the sum of the weights of the two tokens involved.

Executing and proving over dirty ledgers - Stefo, Christos; Xiang, Zhuolun; Kokoris Kogias, Eleftherios (27th International Conference on Financial Cryptography and Data Security)
Scaling blockchain protocols to perform on par with the expected needs of Web3.0 has been proven to be a challenging task with almost a decade of research. In the forefront of the current solution is the idea of separating the execution of the updates encoded in a block from the ordering of blocks. In order to achieve this, a new class of protocols called rollups has emerged. Rollups have as input a total ordering of valid and invalid transactions and as output a new valid state-transition. If we study rollups from a distributed computing perspective, we uncover that rollups take as input the output of a Byzantine Atomic Broadcast (BAB) protocol and convert it to a State Machine Replication (SMR) protocol. BAB and SMR, however, are considered equivalent as far as distributed computing is concerned and a solution to one can easily be retrofitted to solve the other simply by adding/removing an execution step before the validation of the input. This “easy” step of retrofitting an atomic broadcast solution to implement an SMR has, however, been overlooked in practice. In this paper, we formalize the problem and show that after BAB is solved, traditional impossibility results for consensus no longer apply towards an SMR. Leveraging this we propose a distributed execution protocol that allows reduced execution and storage cost per executor (O(log2n/n)) without relaxing the network assumptions of the underlying BAB protocol and providing censorship-resistance. Finally, we propose efficient non-interactive light client constructions that leverage our efficient execution protocols and do not require any synchrony assumptions or expensive ZK-proofs.

Exploring the landscape of heterocyclic quinones for redox flow batteries - Jethwa, Rajesh B; Hey, Dominic; Kerber, Rachel N.; Bond, Andrew D.; Wright, Dominic S.; Grey, Clare P. (ACS Applied Energy Materials)
Redox flow batteries (RFBs) rely on the development of cheap, highly soluble, and high-energy-density electrolytes. Several candidate quinones have already been investigated in the literature as two-electron anolytes or catholytes, benefiting from fast kinetics, high tunability, and low cost. Here, an investigation of nitrogen-rich fused heteroaromatic quinones was carried out to explore avenues for electrolyte development. These quinones were synthesized and screened by using electrochemical techniques. The most promising candidate, 4,8-dioxo-4,8-dihydrobenzo[1,2-d:4,5-d′]bis([1,2,3]triazole)-1,5-diide (−0.68 V(SHE)), was tested in both an asymmetric and symmetric full-cell setup resulting in capacity fade rates of 0.35% per cycle and 0.0124% per cycle, respectively. In situ ultraviolet-visible spectroscopy (UV–Vis), nuclear magnetic resonance (NMR), and electron paramagnetic resonance (EPR) spectroscopies were used to investigate the electrochemical stability of the charged species during operation. UV–Vis spectroscopy, supported by density functional theory (DFT) modeling, reaffirmed that the two-step charging mechanism observed during battery operation consisted of two, single-electron transfers. The radical concentration during battery operation and the degree of delocalization of the unpaired electron were quantified with NMR and EPR spectroscopy.
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Electrochemistry; Energy Engineering and Power Technology; Chemical Engineering (miscellaneous)

Band engineering through Pb-doping of nanocrystal building blocks to enhance thermoelectric performance in Cu3SbSe4 - Wan, Shanhong; Xiao, Shanshan; Li, Mingquan; Wang, Xin; Lim, Khak Ho; Hong, Min; Ibáñez, Maria; Cabot, Andreu; Liu, Yu (Small Methods)
Developing cost-effective and high-performance thermoelectric (TE) materials to assemble efficient TE devices presents a multitude of challenges and opportunities. Cu3SbSe4 is a promising p-type TE material based on relatively earth abundant elements. However, the challenge lies in its poor electrical conductivity. Herein, an efficient and scalable solution-based approach is developed to synthesize high-quality Cu3SbSe4 nanocrystals doped with Pb at the Sb site. After ligand displacement and annealing treatments, the dried powders are consolidated into dense pellets, and their TE properties are investigated. Pb doping effectively increases the charge carrier concentration, resulting in a significant increase in electrical conductivity, while the Seebeck coefficients remain consistently high. The calculated band structure shows that Pb doping induces band convergence, thereby increasing the effective mass. Furthermore, the large ionic radius of Pb2+ results in the generation of additional point and plane defects and interphases, dramatically enhancing phonon scattering, which significantly decreases the lattice thermal conductivity at high temperatures. Overall, a maximum figure of merit (zTmax) ≈ 0.85 at 653 K is obtained in Cu3Sb0.97Pb0.03Se4. This represents a 1.6-fold increase compared to the undoped sample and exceeds most doped Cu3SbSe4-based materials produced by solid-state, demonstrating advantages of versatility and cost-effectiveness using a solution-based technology.

Functional John and Löwner conditions for pairs of log-concave functions - Ivanov, Grigory; Naszódi, Márton (International Mathematics Research Notices)
John’s fundamental theorem characterizing the largest volume ellipsoid contained in a convex body $K$ in $\mathbb{R}^{d}$ has seen several generalizations and extensions. One direction, initiated by V. Milman is to replace ellipsoids by positions (affine images) of another body $L$. Another, more recent direction is to consider logarithmically concave functions on $\mathbb{R}^{d}$ instead of convex bodies: we designate some special, radially symmetric log-concave function $g$ as the analogue of the Euclidean ball, and want to find its largest integral position under the constraint that it is pointwise below some given log-concave function $f$. We follow both directions simultaneously: we consider the functional question, and allow essentially any meaningful function to play the role of $g$ above. Our general theorems jointly extend known results in both directions. The dual problem in the setting of convex bodies asks for the smallest volume ellipsoid, called Löwner’s ellipsoid, containing $K$. We consider the analogous problem for functions: we characterize the solutions of the optimization problem of finding a smallest integral position of some log-concave function $g$ under the constraint that it is pointwise above $f$. It turns out that in the functional setting, the relationship between the John and the Löwner problems is more intricate than it is in the setting of convex bodies.
Keywords: General Mathematics

R2: Boosting liquidity in payment channel networks with online admission control - Bastankhah, Mahsa; Chatterjee, Krishnendu; Maddah-Ali, Mohammad Ali; Schmid, Stefan; Svoboda, Jakub; Yeo, Michelle X (27th International Conference on Financial Cryptography and Data Security)
Payment channel networks (PCNs) are a promising technology to improve the scalability of cryptocurrencies. PCNs, however, face the challenge that the frequent usage of certain routes may deplete channels in one direction, and hence prevent further transactions. In order to reap the full potential of PCNs, recharging and rebalancing mechanisms are required to provision channels, as well as an admission control logic to decide which transactions to reject in case capacity is insufficient. This paper presents a formal model of this optimisation problem. In particular, we consider an online algorithms perspective, where transactions arrive over time in an unpredictable manner. Our main contributions are competitive online algorithms which come with provable guarantees over time. We empirically evaluate our algorithms on randomly generated transactions to compare the average performance of our algorithms to our theoretical bounds. We also show how this model and approach differs from related problems in classic communication networks.

A survey of vectorization methods in topological data analysis - Ali, Dashti; Asaad, Aras; Jimenez, Maria-Jose; Nanda, Vidit; Paluzo-Hidalgo, Eduardo; Soriano Trigueros, Manuel (IEEE Transactions on Pattern Analysis and Machine Intelligence)
Attempts to incorporate topological information in supervised learning tasks have resulted in the creation of several techniques for vectorizing persistent homology barcodes. In this paper, we study thirteen such methods. Besides describing an organizational framework for these methods, we comprehensively benchmark them against three well-known classification tasks. Surprisingly, we discover that the best-performing method is a simple vectorization, which consists only of a few elementary summary statistics. Finally, we provide a convenient web application which has been designed to facilitate exploration and experimentation with various vectorization methods.
Keywords: Applied Mathematics; Artificial Intelligence; Computational Theory and Mathematics; Computer Vision and Pattern Recognition; Software

The impact of chromosomal rearrangements in speciation: From micro- to macroevolution - Lucek, Kay; Giménez, Mabel D.; Joron, Mathieu; Rafajlović, Marina; Searle, Jeremy B.; Walden, Nora; Westram, Anja M; Faria, Rui (Cold Spring Harbor Perspectives in Biology)
Chromosomal rearrangements (CRs) have been known since almost the beginning of genetics. While an important role for CRs in speciation has been suggested, evidence primarily stems from theoretical and empirical studies focusing on the microevolutionary level (i.e., on taxon pairs where speciation is often incomplete). Although the role of CRs in eukaryotic speciation at a macroevolutionary level has been supported by associations between species diversity and rates of evolution of CRs across phylogenies, these findings are limited to a restricted range of CRs and taxa. Now that more broadly applicable and precise CR detection approaches have become available, we address the challenges in filling some of the conceptual and empirical gaps between micro- and macroevolutionary studies on the role of CRs in speciation. We synthesize what is known about the macroevolutionary impact of CRs and suggest new research avenues to overcome the pitfalls of previous studies to gain a more comprehensive understanding of the evolutionary significance of CRs in speciation across the tree of life.
Keywords: General Biochemistry; Genetics and Molecular Biology

Divide & Scale: Formalization and roadmap to robust sharding - Avarikioti, Zeta; Desjardins, Antoine; Kokoris Kogias, Eleftherios; Wattenhofer, Roger (30th International Colloquium on Structural Information and Communication Complexity)
Sharding distributed ledgers is a promising on-chain solution for scaling blockchains but lacks formal grounds, nurturing skepticism on whether such complex systems can scale blockchains securely. We fill this gap by introducing the first formal framework as well as a roadmap to robust sharding. In particular, we first define the properties sharded distributed ledgers should fulfill. We build upon and extend the Bitcoin backbone protocol by defining consistency and scalability. Consistency encompasses the need for atomic execution of cross-shard transactions to preserve safety, whereas scalability encapsulates the speedup a sharded system can gain in comparison to a non-sharded system. Using our model, we explore the limitations of sharding. We show that a sharded ledger with n participants cannot scale under a fully adaptive adversary, but it can scale up to m shards where n=c'm log m, under an epoch-adaptive adversary; the constant c' encompasses the trade-off between security and scalability. This is possible only if the sharded ledgers create succinct proofs of the valid state updates at every epoch. We leverage our results to identify the sufficient components for robust sharding, which we incorporate in a protocol abstraction termed Divide & Scale. To demonstrate the power of our framework, we analyze the most prominent sharded blockchains (Elastico, Monoxide, OmniLedger, RapidChain) and pinpoint where they fail to meet the desired properties.

Monitoring and active stabilization of laser injection locking using beam ellipticity - Mishra, Umang; Li, Vyacheslav; Wald, Sebastian; Agafonova, Sofya; Diorico, Fritz R; Hosten, Onur (Optics Letters)
We unveil a powerful method for the stabilization of laser injection locking based on sensing variations in the output beam ellipticity of an optically seeded laser. The effect arises due to an interference between the seeding beam and the injected laser output. We demonstrate the method for a commercial semiconductor laser without the need for any internal changes to the readily operational injection locked laser system that was used. The method can also be used to increase the mode-hop free tuning range of lasers, and has the potential to fill a void in the low-noise laser industry.
Keywords: Atomic and Molecular Physics; and Optics

How moisture shapes low‐level radiative cooling in subsidence regimes - Fildier, B.; Muller, Caroline J; Pincus, R.; Fueglistaler, S. (AGU Advances)
Radiative cooling of the lowest atmospheric levels is of strong importance for modulating atmospheric circulations and organizing convection, but detailed observations and a robust theoretical understanding are lacking. Here we use unprecedented observational constraints from subsidence regimes in the tropical Atlantic to develop a theory for the shape and magnitude of low‐level longwave radiative cooling in clear‐sky, showing peaks larger than 5–10 K/day at the top of the boundary layer. A suite of novel scaling approximations is first developed from simplified spectral theory, in close agreement with the measurements. The radiative cooling peak height is set by the maximum lapse rate in water vapor path, and its magnitude is mainly controlled by the ratio of column relative humidity above and below the peak. We emphasize how elevated intrusions of moist air can reduce low‐level cooling, by sporadically shading the spectral range which effectively cools to space. The efficiency of this spectral shading depends both on water content and altitude of moist intrusions; its height dependence cannot be explained by the temperature difference between the emitting and absorbing layers, but by the decrease of water vapor extinction with altitude. This analytical work can help to narrow the search for low‐level cloud patterns sensitive to radiative‐convective feedbacks: the most organized patterns with largest cloud fractions occur in atmospheres below 10% relative humidity and feel the strongest low‐level cooling. This motivates further assessment of favorable conditions for radiative‐convective feedbacks and a robust quantification of corresponding shallow cloud dynamics in current and warmer climates.
Keywords: General Earth and Planetary Sciences

Mean structure of the supercritical turbulent spiral in Taylor–Couette flow - Wang, B.; Mellibovsky, F.; Ayats López, Roger; Deguchi, K.; Meseguer, A. (Philosophical Transactions of the Royal Society A)
The large-scale laminar/turbulent spiral patterns that appear in the linearly unstable regime of counter-rotating Taylor–Couette flow are investigated from a statistical perspective by means of direct numerical simulation. Unlike the vast majority of previous numerical studies, we analyse the flow in periodic parallelogram-annular domains, following a coordinate change that aligns one of the parallelogram sides with the spiral pattern. The domain size, shape and spatial resolution have been varied and the results compared with those in a sufficiently large computational orthogonal domain with natural axial and azimuthal periodicity. We find that a minimal parallelogram of the right tilt significantly reduces the computational cost without notably compromising the statistical properties of the supercritical turbulent spiral. Its mean structure, obtained from extremely long time integrations in a co-rotating reference frame using the method of slices, bears remarkable similarity with the turbulent stripes observed in plane Couette flow, the centrifugal instability playing only a secondary role.
Keywords: General Physics and Astronomy; General Engineering; General Mathematics

Low-pT quarkonium polarization measurements: Challenges and opportunities - Faccioli, Pietro; Krätschmer, Ilse; Lourenço, Carlos (Physics Letters B)
Several fixed-target experiments reported J/ψ and ϒ polarizations, as functions of Feynman x (xF) and transverse momentum (PT), in three different frames, using different combinations of beam particles, target nuclei, and collision energies. Despite the diverse and heterogeneous picture formed by these measurements, a detailed look allows us to discern qualitative physical patterns that inspire a simple empirical model. This data-driven scenario offers a good quantitative description of the J/ψ and ϒ(1S) polarizations measured in proton- and pion-nucleus collisions, in the xF 0.5 domain: more than 80 data points (not statistically independent) are well reproduced with only one free parameter. This study sets the context for future low-PT quarkonium polarization measurements in proton- and pion-nucleus collisions, such as those to be made by the AMBER experiment, and shows that such measurements provide significant constraints on the poorly-known parton distribution functions of the pion.
Keywords: Nuclear and High Energy Physics

Local laws for multiplication of random matrices - Ding, Xiucai; Ji, Hong Chang (The Annals of Applied Probability)
Consider the random matrix model A1/2UBU∗A1/2, where A and B are two N × N deterministic matrices and U is either an N × N Haar unitary or orthogonal random matrix. It is well known that on the macroscopic scale (Invent. Math. 104 (1991) 201–220), the limiting empirical spectral distribution (ESD) of the above model is given by the free multiplicative convolution of the limiting ESDs of A and B, denoted as μα μβ, where μα and μβ are the limiting ESDs of A and B, respectively. In this paper, we study the asymptotic microscopic behavior of the edge eigenvalues and eigenvectors statistics. We prove that both the density of μA μB, where μA and μB are the ESDs of A and B, respectively and the associated subordination functions have a regular behavior near the edges. Moreover, we establish the local laws near the edges on the optimal scale. In particular, we prove that the entries of the resolvent are close to some functionals depending only on the eigenvalues of A, B and the subordination functions with optimal convergence rates. Our proofs and calculations are based on the techniques developed for the additive model A+UBU∗ in (J. Funct. Anal. 271 (2016) 672–719; Comm. Math. Phys. 349 (2017) 947–990; Adv. Math. 319 (2017) 251–291; J. Funct. Anal. 279 (2020) 108639), and our results can be regarded as the counterparts of (J. Funct. Anal. 279 (2020) 108639) for the multiplicative model.
Keywords: Statistics; Probability and Uncertainty; Statistics and Probability

Fully extended r-spin TQFTs - Carqueville, Nils; Szegedy, Lorant (Quantum Topology)
We prove the r-spin cobordism hypothesis in the setting of (weak) 2-categories for every positive integer r: the 2-groupoid of 2-dimensional fully extended r-spin TQFTs with given target is equivalent to the homotopy fixed points of an induced Spin 2r -action. In particular, such TQFTs are classified by fully dualisable objects together with a trivialisation of the rth power of their Serre automorphisms. For r=1, we recover the oriented case (on which our proof builds), while ordinary spin structures correspond to r=2. To construct examples, we explicitly describe Spin 2r​-homotopy fixed points in the equivariant completion of any symmetric monoidal 2-category. We also show that every object in a 2-category of Landau–Ginzburg models gives rise to fully extended spin TQFTs and that half of these do not factor through the oriented bordism 2-category.
Keywords: Geometry and Topology; Mathematical Physics

Zero-error communication over adversarial MACs - Zhang, Yihan (IEEE Transactions on Information Theory)
We consider zero-error communication over a two-transmitter deterministic adversarial multiple access channel (MAC) governed by an adversary who has access to the transmissions of both senders (hence called omniscient ) and aims to maliciously corrupt the communication. None of the encoders, jammer and decoder is allowed to randomize using private or public randomness. This enforces a combinatorial nature of the problem. Our model covers a large family of channels studied in the literature, including all deterministic discrete memoryless noisy or noiseless MACs. In this work, given an arbitrary two-transmitter deterministic omniscient adversarial MAC, we characterize when the capacity region: 1) has nonempty interior (in particular, is two-dimensional); 2) consists of two line segments (in particular, has empty interior); 3) consists of one line segment (in particular, is one-dimensional); 4) or only contains (0,0) (in particular, is zero-dimensional). This extends a recent result by Wang et al. (201 9) from the point-to-point setting to the multiple access setting. Indeed, our converse arguments build upon their generalized Plotkin bound and involve delicate case analysis. One of the technical challenges is to take care of both “joint confusability” and “marginal confusability”. In particular, the treatment of marginal confusability does not follow from the point-to-point results by Wang et al. Our achievability results follow from random coding with expurgation.
Keywords: Computer Science Applications; Information Systems

Convergence of the scalar- and vector-valued Allen–Cahn equation to mean curvature flow with 90°-contact angle in higher dimensions, part I: Convergence result - Moser, Maximilian (Asymptotic Analysis)
We consider the sharp interface limit for the scalar-valued and vector-valued Allen–Cahn equation with homogeneous Neumann boundary condition in a bounded smooth domain Ω of arbitrary dimension N ⩾ 2 in the situation when a two-phase diffuse interface has developed and intersects the boundary ∂ Ω. The limit problem is mean curvature flow with 90°-contact angle and we show convergence in strong norms for well-prepared initial data as long as a smooth solution to the limit problem exists. To this end we assume that the limit problem has a smooth solution on [ 0 , T ] for some time T > 0. Based on the latter we construct suitable curvilinear coordinates and set up an asymptotic expansion for the scalar-valued and the vector-valued Allen–Cahn equation. In order to estimate the difference of the exact and approximate solutions with a Gronwall-type argument, a spectral estimate for the linearized Allen–Cahn operator in both cases is required. The latter will be shown in a separate paper, cf. (Moser (2021)).
Keywords: General Mathematics

Interplay of Cell‐autonomous Gene Function and Tissue‐wide Mechanisms Regulating Radial Glial Progenitor Lineage Progression - Villalba Requena, Ana; Amberg, Nicole; Hippenmeyer, Simon (Neocortical Neurogenesis in Development and Evolution)
The cerebral cortex is comprised of a vast cell-type diversity sequentially generated by cortical progenitor cells. Faithful progenitor lineage progression requires the tight orchestration of distinct molecular and cellular mechanisms regulating proper progenitor proliferation behavior and differentiation. Correct execution of developmental programs involves a complex interplay of cell intrinsic and tissue-wide mechanisms. Many studies over the past decades have been able to determine a plethora of genes critically involved in cortical development. However, only a few made use of genetic paradigms with sparse and global gene deletion to probe cell-autonomous vs. tissue-wide contribution. In this chapter, we will elaborate on the importance of dissecting the cell-autonomous and tissue-wide mechanisms to gain a precise understanding of gene function during radial glial progenitor lineage progression.

Analog stabilization of an electro-optic I/Q modulator with an auxiliary modulation tone - Wald, Sebastian; Diorico, Fritz R; Hosten, Onur (Applied Optics)
Proper operation of electro-optic I/Q modulators relies on precise adjustment and control of the relative phase biases between the modulator’s internal interferometer arms. We present an all-analog phase bias locking scheme where error signals are obtained from the beat between the optical carrier and optical tones generated by an auxiliary 2 MHz 𝑅𝐹 tone to lock the phases of all three involved interferometers for operation up to 10 GHz. With the developed method, we demonstrate an I/Q modulator in carrier-suppressed single-sideband mode, where the suppressed carrier and sideband are locked at optical power levels <−27dB relative to the transmitted sideband. We describe a simple analytical model for calculating the error signals and detail the implementation of the electronic circuitry for the implementation of the method.
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Research data for the publication "Dense 4D nanoscale reconstruction of living brain tissue" - Danzl, Johann G
3D-reconstruction of living brain tissue down to individual synapse level would create opportunities for decoding the dynamics and structure-function relationships of the brain’s complex and dense information processing network. However, it has been hindered by insufficient 3D-resolution, inadequate signal-to-noise-ratio, and prohibitive light burden in optical imaging, whereas electron microscopy is inherently static. Here we solved these challenges by developing an integrated optical/machine learning technology, LIONESS (Live Information-Optimized Nanoscopy Enabling Saturated Segmentation). It leverages optical modifications to stimulated emission depletion (STED) microscopy in comprehensively, extracellularly labelled tissue and prior information on sample structure via machine learning to simultaneously achieve isotropic super-resolution, high signal-to-noise-ratio, and compatibility with living tissue. This allows dense deep-learning-based instance segmentation and 3D-reconstruction at synapse level incorporating molecular, activity, and morphodynamic information. LIONESS opens up avenues for studying the dynamic functional (nano-)architecture of living brain tissue.

Dense 4D nanoscale reconstruction of living brain tissue - Velicky, Philipp; Miguel Villalba, Eder; Michalska, Julia M; Lyudchik, Julia; Wei, Donglai; Lin, Zudi; Watson, Jake; Troidl, Jakob; Beyer, Johanna; Ben Simon, Yoav; Sommer, Christoph M; Jahr, Wiebke; et al. (Nature Methods)
Three-dimensional (3D) reconstruction of living brain tissue down to an individual synapse level would create opportunities for decoding the dynamics and structure–function relationships of the brain’s complex and dense information processing network; however, this has been hindered by insufficient 3D resolution, inadequate signal-to-noise ratio and prohibitive light burden in optical imaging, whereas electron microscopy is inherently static. Here we solved these challenges by developing an integrated optical/machine-learning technology, LIONESS (live information-optimized nanoscopy enabling saturated segmentation). This leverages optical modifications to stimulated emission depletion microscopy in comprehensively, extracellularly labeled tissue and previous information on sample structure via machine learning to simultaneously achieve isotropic super-resolution, high signal-to-noise ratio and compatibility with living tissue. This allows dense deep-learning-based instance segmentation and 3D reconstruction at a synapse level, incorporating molecular, activity and morphodynamic information. LIONESS opens up avenues for studying the dynamic functional (nano-)architecture of living brain tissue.

Bias in pruned vision models: In-depth analysis and countermeasures - Iofinova, Eugenia B; Peste, Elena-Alexandra; Alistarh, Dan-Adrian (2023 IEEE/CVF Conference on Computer Vision and Pattern Recognition)
Pruning—that is, setting a significant subset of the parameters of a neural network to zero—is one of the most popular methods of model compression. Yet, several recent works have raised the issue that pruning may induce or exacerbate bias in the output of the compressed model. Despite existing evidence for this phenomenon, the relationship between neural network pruning and induced bias is not well-understood. In this work, we systematically investigate and characterize this phenomenon in Convolutional Neural Networks for computer vision. First, we show that it is in fact possible to obtain highly-sparse models, e.g. with less than 10% remaining weights, which do not decrease in accuracy nor substantially increase in bias when compared to dense models. At the same time, we also find that, at higher sparsities, pruned models exhibit higher uncertainty in their outputs, as well as increased correlations, which we directly link to increased bias. We propose easy-to-use criteria which, based only on the uncompressed model, establish whether bias will increase with pruning, and identify the samples most susceptible to biased predictions post-compression. Our code can be found at https://github.com/IST-DASLab/pruned-vision-model-bias.

LIONESS enables 4D nanoscale reconstruction of living brain tissue - Danzl, Johann G; Velicky, Philipp (Nature Methods)
We developed LIONESS, a technology that leverages improvements to optical super-resolution microscopy and prior information on sample structure via machine learning to overcome the limitations (in 3D-resolution, signal-to-noise ratio and light exposure) of optical microscopy of living biological specimens. LIONESS enables dense reconstruction of living brain tissue and morphodynamics visualization at the nanoscale.
Keywords: Cell Biology; Molecular Biology; Biochemistry; Biotechnology

Real-time monitoring of an endogenous Fgf8a gradient attests to its role as a morphogen during zebrafish gastrulation - Harish, Rohit K; Gupta, Mansi; Zöller, Daniela; Hartmann, Hella; Gheisari, Ali; Machate, Anja; Hans, Stefan; Brand, Michael (Development)
Morphogen gradients impart positional information to cells in a homogenous tissue field. Fgf8a, a highly conserved growth factor, has been proposed to act as a morphogen during zebrafish gastrulation. However, technical limitations have so far prevented direct visualization of the endogenous Fgf8a gradient and confirmation of its morphogenic activity. Here, we monitor Fgf8a propagation in the developing neural plate using a CRISPR/Cas9-mediated EGFP knock-in at the endogenous fgf8a locus. By combining sensitive imaging with single-molecule fluorescence correlation spectroscopy, we demonstrate that Fgf8a, which is produced at the embryonic margin, propagates by diffusion through the extracellular space and forms a graded distribution towards the animal pole. Overlaying the Fgf8a gradient curve with expression profiles of its downstream targets determines the precise input-output relationship of Fgf8a-mediated patterning. Manipulation of the extracellular Fgf8a levels alters the signaling outcome, thus establishing Fgf8a as a bona fide morphogen during zebrafish gastrulation. Furthermore, by hindering Fgf8a diffusion, we demonstrate that extracellular diffusion of the protein from the source is crucial for it to achieve its morphogenic potential.
Keywords: Developmental Biology; Molecular Biology

Phytaspase Is capable of detaching the endoplasmic reticulum retrieval signal from tobacco calreticulin-3 - Teplova, Anastasiia; Pigidanov, Artemii A.; Serebryakova, Marina V.; Golyshev, Sergei A.; Galiullina, Raisa A.; Chichkova, Nina V.; Vartapetian, Andrey B. (International Journal of Molecular Sciences)
Soluble chaperones residing in the endoplasmic reticulum (ER) play vitally important roles in folding and quality control of newly synthesized proteins that transiently pass through the ER en route to their final destinations. These soluble residents of the ER are themselves endowed with an ER retrieval signal that enables the cell to bring the escaped residents back from the Golgi. Here, by using purified proteins, we showed that Nicotiana tabacum phytaspase, a plant aspartate-specific protease, introduces two breaks at the C-terminus of the N. tabacum ER resident calreticulin-3. These cleavages resulted in removal of either a dipeptide or a hexapeptide from the C-terminus of calreticulin-3 encompassing part or all of the ER retrieval signal. Consistently, expression of the calreticulin-3 derivative mimicking the phytaspase cleavage product in Nicotiana benthamiana cells demonstrated loss of the ER accumulation of the protein. Notably, upon its escape from the ER, calreticulin-3 was further processed by an unknown protease(s) to generate the free N-terminal (N) domain of calreticulin-3, which was ultimately secreted into the apoplast. Our study thus identified a specific proteolytic enzyme capable of precise detachment of the ER retrieval signal from a plant ER resident protein, with implications for the further fate of the escaped resident.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Convergence rate to the Tracy–Widom laws for the largest eigenvalue of sample covariance matrices - Schnelli, Kevin; Xu, Yuanyuan (The Annals of Applied Probability)
We establish a quantitative version of the Tracy–Widom law for the largest eigenvalue of high-dimensional sample covariance matrices. To be precise, we show that the fluctuations of the largest eigenvalue of a sample covariance matrix X∗X converge to its Tracy–Widom limit at a rate nearly N−1/3, where X is an M×N random matrix whose entries are independent real or complex random variables, assuming that both M and N tend to infinity at a constant rate. This result improves the previous estimate N−2/9 obtained by Wang (2019). Our proof relies on a Green function comparison method (Adv. Math. 229 (2012) 1435–1515) using iterative cumulant expansions, the local laws for the Green function and asymptotic properties of the correlation kernel of the white Wishart ensemble.
Keywords: Statistics; Probability and Uncertainty; Statistics and Probability

The cloud dynamics of convective storm systems - Muller, Caroline J; Abramian, Sophie (Physics Today)
Through a combination of idealized simulations and real-world data, researchers are uncovering how internal feedbacks and large-scale motions influence cloud dynamics.
Keywords: General Physics and Astronomy

Improvement of thermoelectric performance of flexible compound Ag2S0.55Se0.45 by means of partial V-substitution for Ag - Sato, Kosuke; Singh, Saurabh; Yamazaki, Itsuki; Hirata, Keisuke; Ang, Artoni Kevin R.; Matsunami, Masaharu; Takeuchi, Tsunehiro (AIP Advances)
The effects of the partial V-substitution for Ag on the thermoelectric (TE) properties are investigated for a flexible semiconducting compound Ag2S0.55Se0.45. Density functional theory calculations predict that such a partial V-substitution constructively modifies the electronic structure near the bottom of the conduction band to improve the TE performance. The synthesized Ag1.97V0.03S0.55Se0.45 is found to possess a TE dimensionless figure-of-merit (ZT) of 0.71 at 350 K with maintaining its flexible nature. This ZT value is relatively high in comparison with those reported for flexible TE materials below 360 K. The increase in the ZT value is caused by the enhanced absolute value of the Seebeck coefficient with less significant variation in electrical resistivity. The high ZT value with the flexible nature naturally allows us to employ the Ag1.97V0.03S0.55Se0.45 as a component of flexible TE generators.
Keywords: General Physics and Astronomy

Divergence of separated nets with respect to displacement equivalence - Dymond, Michael; Kaluza, Vojtech (Geometriae Dedicata)
We introduce a hierachy of equivalence relations on the set of separated nets of a given Euclidean space, indexed by concave increasing functions ϕ:(0,∞)→(0,∞). Two separated nets are called ϕ-displacement equivalent if, roughly speaking, there is a bijection between them which, for large radii R, displaces points of norm at most R by something of order at most ϕ(R). We show that the spectrum of ϕ-displacement equivalence spans from the established notion of bounded displacement equivalence, which corresponds to bounded ϕ, to the indiscrete equivalence relation, coresponding to ϕ(R)∈Ω(R), in which all separated nets are equivalent. In between the two ends of this spectrum, the notions of ϕ-displacement equivalence are shown to be pairwise distinct with respect to the asymptotic classes of ϕ(R) for R→∞. We further undertake a comparison of our notion of ϕ-displacement equivalence with previously studied relations on separated nets. Particular attention is given to the interaction of the notions of ϕ-displacement equivalence with that of bilipschitz equivalence.

Deterministic clustering in high dimensional spaces: Sketches and approximation - Cohen-Addad, Vincent; Saulpic, David; Schwiegelshohn, Chris (2023 IEEE 64th Annual Symposium on Foundations of Computer Science)
In all state-of-the-art sketching and coreset techniques for clustering, as well as in the best known fixed-parameter tractable approximation algorithms, randomness plays a key role. For the classic k-median and k-means problems, there are no known deterministic dimensionality reduction procedure or coreset construction that avoid an exponential dependency on the input dimension d, the precision parameter $ε^{-1}$ or k. Furthermore, there is no coreset construction that succeeds with probability $1-1/n$ and whose size does not depend on the number of input points, n. This has led researchers in the area to ask what is the power of randomness for clustering sketches [Feldman WIREs Data Mining Knowl. Discov’20].Similarly, the best approximation ratio achievable deterministically without a complexity exponential in the dimension are $1+\sqrt{2}$ for k-median [Cohen-Addad, Esfandiari, Mirrokni, Narayanan, STOC’22] and 6.12903 for k-means [Grandoni, Ostrovsky, Rabani, Schulman, Venkat, Inf. Process. Lett.’22]. Those are the best results, even when allowing a complexity FPT in the number of clusters k: this stands in sharp contrast with the $(1+ε)$-approximation achievable in that case, when allowing randomization.In this paper, we provide deterministic sketches constructions for clustering, whose size bounds are close to the best-known randomized ones. We show how to compute a dimension reduction onto $ε^{-O(1)} \log k$ dimensions in time $k^{O\left(ε^{-O(1)}+\log \log k\right)}$ poly $(n d)$, and how to build a coreset of size $O\left(k^{2} \log ^{3} k ε^{-O(1)}\right)$ in time $2^{ε^{O(1)} k \log ^{3} k}+k^{O\left(ε^{-O(1)}+\log \log k\right)}$ poly $(n d)$. In the case where k is small, this answers an open question of [Feldman WIDM’20] and [Munteanu and Schwiegelshohn, Künstliche Intell. ’18] on whether it is possible to efficiently compute coresets deterministically.We also construct a deterministic algorithm for computing $(1+$ $ε)$-approximation to k-median and k-means in high dimensional Euclidean spaces in time $2^{k^{2} \log ^{3} k / ε^{O(1)}}$ poly $(n d)$, close to the best randomized complexity of $2^{(k / ε)^{O(1)}}$ nd (see [Kumar, Sabharwal, Sen, JACM 10] and [Bhattacharya, Jaiswal, Kumar, TCS’18]).Furthermore, our new insights on sketches also yield a randomized coreset construction that uses uniform sampling, that immediately improves over the recent results of [Braverman et al. FOCS ’22] by a factor k.

Exposure of volunteers to microgravity by dry immersion bed over 21 days results in gene expression changes and adaptation of T cells - Gallardo-Dodd, Carlos J.; Oertlin, Christian; Record, Julien; Galvani, Rômulo G.; Sommerauer, Christian; Kuznetsov, Nikolai V.; Doukoumopoulos, Evangelos; Ali, Liaqat; Oliveira, Mariana M. S.; Seitz, Christina; Percipalle, Mathias; Nikić, Tijana; et al. (Science Advances)
The next steps of deep space exploration are manned missions to Moon and Mars. For safe space missions for crew members, it is important to understand the impact of space flight on the immune system. We studied the effects of 21 days dry immersion (DI) exposure on the transcriptomes of T cells isolated from blood samples of eight healthy volunteers. Samples were collected 7 days before DI, at day 7, 14, and 21 during DI, and 7 days after DI. RNA sequencing of CD3+T cells revealed transcriptional alterations across all time points, with most changes occurring 14 days after DI exposure. At day 21, T cells showed evidence of adaptation with a transcriptional profile resembling that of 7 days before DI. At 7 days after DI, T cells again changed their transcriptional profile. These data suggest that T cells adapt by rewiring their transcriptomes in response to simulated weightlessness and that remodeling cues persist when reexposed to normal gravity.
Keywords: Multidisciplinary

Branched actin cortices reconstituted in vesicles sense membrane curvature - Baldauf, Lucia; Frey, Felix F; Arribas Perez, Marcos; Idema, Timon; Koenderink, Gijsje H. (Biophysical Journal)
The actin cortex is a complex cytoskeletal machinery that drives and responds to changes in cell shape. It must generate or adapt to plasma membrane curvature to facilitate diverse functions such as cell division, migration, and phagocytosis. Due to the complex molecular makeup of the actin cortex, it remains unclear whether actin networks are inherently able to sense and generate membrane curvature, or whether they rely on their diverse binding partners to accomplish this. Here, we show that curvature sensing is an inherent capability of branched actin networks nucleated by Arp2/3 and VCA. We develop a robust method to encapsulate actin inside giant unilamellar vesicles (GUVs) and assemble an actin cortex at the inner surface of the GUV membrane. We show that actin forms a uniform and thin cortical layer when present at high concentration and distinct patches associated with negative membrane curvature at low concentration. Serendipitously, we find that the GUV production method also produces dumbbell-shaped GUVs, which we explain using mathematical modeling in terms of membrane hemifusion of nested GUVs. We find that branched actin networks preferentially assemble at the neck of the dumbbells, which possess a micrometer-range convex curvature comparable with the curvature of the actin patches found in spherical GUVs. Minimal branched actin networks can thus sense membrane curvature, which may help mammalian cells to robustly recruit actin to curved membranes to facilitate diverse cellular functions such as cytokinesis and migration.
Keywords: Biophysics

Astroglial connexin 43 regulates synaptic vesicle release at hippocampal synapses - Cheung, Giselle T; Chever, Oana; Rollenhagen, Astrid; Quenech’du, Nicole; Ezan, Pascal; Lübke, Joachim H. R.; Rouach, Nathalie (Cells)
Connexin 43, an astroglial gap junction protein, is enriched in perisynaptic astroglial processes and plays major roles in synaptic transmission. We have previously found that astroglial Cx43 controls synaptic glutamate levels and allows for activity-dependent glutamine release to sustain physiological synaptic transmissions and cognitiogns. However, whether Cx43 is important for the release of synaptic vesicles, which is a critical component of synaptic efficacy, remains unanswered. Here, using transgenic mice with a glial conditional knockout of Cx43 (Cx43−/−), we investigate whether and how astrocytes regulate the release of synaptic vesicles from hippocampal synapses. We report that CA1 pyramidal neurons and their synapses develop normally in the absence of astroglial Cx43. However, a significant impairment in synaptic vesicle distribution and release dynamics were observed. In particular, the FM1-43 assays performed using two-photon live imaging and combined with multi-electrode array stimulation in acute hippocampal slices, revealed a slower rate of synaptic vesicle release in Cx43−/− mice. Furthermore, paired-pulse recordings showed that synaptic vesicle release probability was also reduced and is dependent on glutamine supply via Cx43 hemichannel (HC). Taken together, we have uncovered a role for Cx43 in regulating presynaptic functions by controlling the rate and probability of synaptic vesicle release. Our findings further highlight the significance of astroglial Cx43 in synaptic transmission and efficacy.
Keywords: General Medicine

Role of natural transformation in the evolution of small cryptic plasmids in Synechocystis sp. PCC 6803 - Nies, Fabian; Wein, Tanita; Hanke, Dustin M.; Springstein, Benjamin L; Alcorta, Jaime; Taubenheim, Claudia; Dagan, Tal (Environmental Microbiology Reports)
Small cryptic plasmids have no clear effect on the host fitness and their functional repertoire remains obscure. The naturally competent cyanobacterium Synechocystis sp. PCC 6803 harbours several small cryptic plasmids; whether their evolution with this species is supported by horizontal transfer remains understudied. Here, we show that the small cryptic plasmid DNA is transferred in the population exclusively by natural transformation, where the transfer frequency of plasmid‐encoded genes is similar to that of chromosome‐encoded genes. Establishing a system to follow gene transfer, we compared the transfer frequency of genes encoded in cryptic plasmids pCA2.4 (2378 bp) and pCB2.4 (2345 bp) within and between populations of two Synechocystis sp. PCC 6803 labtypes (termed Kiel and Sevilla). Our results reveal that plasmid gene transfer frequency depends on the recipient labtype. Furthermore, gene transfer via whole plasmid uptake in the Sevilla labtype ranged among the lowest detected transfer rates in our experiments. Our study indicates that horizontal DNA transfer via natural transformation is frequent in the evolution of small cryptic plasmids that reside in naturally competent organisms. Furthermore, we suggest that the contribution of natural transformation to cryptic plasmid persistence in Synechocystis is limited.
Keywords: Agricultural and Biological Sciences (miscellaneous); Ecology; Evolution; Behavior and Systematics

Spiked multiplicative random matrices and principal components - Ding, Xiucai; Ji, Hong Chang (Stochastic Processes and their Applications)
In this paper, we study the eigenvalues and eigenvectors of the spiked invariant multiplicative models when the randomness is from Haar matrices. We establish the limits of the outlier eigenvalues λˆi and the generalized components (⟨v,uˆi⟩ for any deterministic vector v) of the outlier eigenvectors uˆi with optimal convergence rates. Moreover, we prove that the non-outlier eigenvalues stick with those of the unspiked matrices and the non-outlier eigenvectors are delocalized. The results also hold near the so-called BBP transition and for degenerate spikes. On one hand, our results can be regarded as a refinement of the counterparts of [12] under additional regularity conditions. On the other hand, they can be viewed as an analog of [34] by replacing the random matrix with i.i.d. entries with Haar random matrix.
Keywords: Applied Mathematics; Modeling and Simulation; Statistics and Probability